Adhesive sheet, optical member, and touch panel
Patent Information
- Application Number
- CN202180041424.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Priority Date
- 2020-06-12
- Filing Date
- 2021-06-09
- Publication Date
- 2026-10-09
- Estimated Expiration
- 2041-06-09
AI Technical Summary
[0005]金属网薄膜、银纳米线薄膜中使用的银、铜有容易引起向粘合剂层的离子迁移、容易因电气噪音而容易产生触摸面板的误动作的问题,随着粘合剂层薄型化,该问题变得更显著
[0059] The adhesive sheet of the present invention has an adhesive layer with low dielectric constant, good adhesion at high temperatures, high adhesion reliability, and excellent height difference tracking. Therefore, by using the adhesive sheet of the present invention to bond metal mesh films and silver nanowire films, it is possible to effectively manufacture high-performance optical components such as touch panels that maintain adhesion at high temperatures, have good adhesion reliability, exhibit excellent height difference absorption with sufficient height difference tracking to avoid residual air bubbles, and are less prone to malfunction.
Smart Images

Figure CN115702227B_ABST
Abstract
Description
Technical Field
[0001] This invention relates to adhesive sheets, optical components, and touch panels. Background Technology
[0002] In recent years, display devices such as liquid crystal displays (LCDs) and input devices such as touch panels used in conjunction with such display devices have been increasingly widely used in various fields. In these display devices and input devices, adhesive sheets with adhesive layers are used for bonding optical components. For example, transparent adhesive sheets are used in bonding touch panels to various display components and optical components (see, for example, Patent Documents 1-3).
[0003] In applications such as the manufacture of capacitive touch panels, adhesive sheets are sometimes directly attached to metal films or metal oxide films such as ITO (indium tin oxide) films (hereinafter, metal films and metal oxide films are sometimes collectively referred to as "metal films").
[0004] In recent years, in applications such as the manufacture of capacitive touch panels, there has been an increasing trend of using thin films with metal mesh wiring formed by processing metals such as silver and copper into a mesh (metal mesh film) and thin films with silver nanowire layers (AgNW layers) to replace conventional ITO films. Capacitive touch panels using metal mesh films and silver nanowire films utilize the low-resistance characteristics of metal wiring to provide highly sensitive input devices suitable for a wide range of displays, from small to large sizes.
[0005] The silver and copper used in metal mesh films and silver nanowire films have problems such as easy ion migration to the adhesive layer and easy malfunction of touch panel due to electrical noise. As the adhesive layer becomes thinner, this problem becomes more significant.
[0006] To suppress erroneous operation of the touch panel, research is underway on using an adhesive layer containing an acrylic polymer with a low dielectric constant to improve the insulating resistance of the adhesive layer itself (for example, see Patent Document 4).
[0007] In addition, research is also being conducted on reducing the dielectric constant of the adhesive layer by incorporating materials with low dielectric constants into the adhesive composition (for example, see Patent Documents 5 and 6).
[0008] Existing technical documents
[0009] Patent documents
[0010] Patent Document 1: Japanese Patent Application Publication No. 2003-238915
[0011] Patent Document 2: Japanese Patent Application Publication No. 2003-342542
[0012] Patent Document 3: Japanese Patent Application Publication No. 2004-231723
[0013] Patent Document 4: Japanese Patent Application Publication No. 2016-172865
[0014] Patent Document 5: Japanese Patent Application Publication No. 2019-038947
[0015] Patent Document 6: Japanese Patent Application Publication No. 2019-182928 Summary of the Invention
[0016] The problem the invention aims to solve
[0017] Acrylic polymers with low dielectric constants are composed of monomers with low polarity and high glass transition temperature of homopolymers. They are hard polymers with high glass transition temperature and low stress relief. Therefore, they cannot fully follow the height difference formed by metal wiring, etc., and have problems such as easy retention of air bubbles and poor height difference tracking.
[0018] To improve the stress relief properties of acrylic polymers with low dielectric constants, reducing the molecular weight was also considered. However, this resulted in a decrease in gelation rate, making it more difficult to maintain adhesive strength and reliability at high temperatures.
[0019] Therefore, the object of the present invention is to provide an adhesive sheet with low dielectric constant, good adhesion at high temperatures, good adhesion reliability, excellent height difference tracking, and suitable for bonding with metal mesh films, etc.
[0020] Another objective of the present invention is to provide a high-performance optical component and a touch panel that incorporates the adhesive sheet and is less prone to malfunction.
[0021] Solution for solving the problem
[0022] In order to achieve the above-mentioned objectives, the inventors conducted in-depth research and found that by using an acrylic polymer as the base polymer constituting the adhesive layer and blending it with a polyolefin resin of a specific composition, it is possible to form an adhesive sheet with low dielectric constant, good adhesion at high temperatures, good adhesion reliability, excellent height difference tracking, and suitable for bonding metal mesh films and silver nanowire films, thus completing the present invention.
[0023] A first aspect of the present invention provides an adhesive sheet having an adhesive layer. In this first aspect, the dielectric constant of the adhesive layer at a frequency of 1 MHz is 2.3 to 3.5. This configuration is preferred from the viewpoint that it can prevent malfunctions caused by ion migration, etc., when the adhesive sheet of the first aspect of the present invention is bonded to a thin film with metal wiring, such as a metal mesh film or a silver nanowire film.
[0024] In a first aspect of the present invention, the aforementioned adhesive layer comprises an acrylic polymer (A) and a hydrogenated polyolefin resin (B) that exhibits liquid flowability at 25°C.
[0025] In the first aspect of the present invention, it is preferable that the composition of the aforementioned adhesive layer containing an acrylic polymer (A) allows for a low dielectric constant in the adhesive layer by adjusting the monomer composition. However, in order to make the adhesive layer have a low dielectric constant, the monomer components constituting the acrylic polymer (A) need to be low polarity monomer components with high glass transition temperature (Tg) of homopolymers (e.g., Tg: -80 to 0°C). Therefore, the acrylic polymer (A) becomes a (hard) polymer with a high glass transition temperature and low stress relief, which cannot adequately follow the height difference formed by metal wiring, etc., and sometimes air bubbles are easily left behind, resulting in poor height difference tracking. When the molecular weight is reduced to improve the stress relief of the acrylic polymer (A), there is a problem that the gelation rate decreases, making it difficult to maintain the adhesive strength and adhesive reliability at high temperatures.
[0026] In the first aspect of the present invention, the aforementioned adhesive layer comprising a hydrogenated polyolefin resin (B) exhibiting liquid flowability at 25°C is preferred in that it maintains adhesive strength and adhesive reliability at high temperatures without reducing the molecular weight of the acrylic polymer (A), and improves stress relief and imparts excellent height difference tracking to the adhesive layer. The hydrogenated polyolefin resin (B) is a material with a low dielectric constant and exhibits liquid flowability at 25°C (room temperature). Therefore, by incorporating it into the acrylic polymer (A), the stress relief of the adhesive layer can be improved without increasing the dielectric constant, thereby enhancing height difference tracking.
[0027] Furthermore, by including hydrogenated polyolefin resin (B) in the aforementioned adhesive layer, stress relief can be improved without reducing the molecular weight of the acrylic polymer (A). Moreover, because the carbon-carbon double bonds in the hydrogenated polyolefin resin (B) are reduced through hydrogenation, the number of carbon-carbon double bonds in the molecule decreases. Therefore, polymerization inhibition is less likely to occur when the adhesive layer is cured by ultraviolet irradiation, and the polymerization rate is less likely to decrease or the molecular weight is reduced. Thus, the adhesive strength and bonding reliability of the adhesive sheet of the first aspect of the present invention can be highly maintained at high temperatures.
[0028] In addition, hydrogenated polyolefin resin (B) is also preferred in terms of maintaining the transparency of the adhesive layer to a greater extent because it has excellent compatibility with acrylic polymer (A).
[0029] Therefore, the first aspect of the present invention provides an adhesive sheet that, by comprising an acrylic polymer (A) and a hydrogenated polyolefin resin (B) in the aforementioned adhesive layer, provides a high degree of adhesive strength and reliability at high temperatures, and has a low dielectric constant, excellent height difference tracking, and is preferably used for attachment to transparent conductive films with metal wiring layers such as metal mesh films and silver nanowire films.
[0030] As described above, the adhesive sheet of the first aspect of the present invention can achieve high-temperature adhesion and high adhesion reliability to transparent conductive films with metal wiring layers, such as metal mesh films and silver nanowire films. Specifically, the adhesive sheet of the first aspect of the present invention has a 180° peel adhesion force of 6 N / 20 mm or more to a glass plate at 65°C and a tensile speed of 300 mm / min.
[0031] Furthermore, the ratio of the 180° peel bond strength of the adhesive sheet of the first aspect of the present invention to the glass plate at 65°C and a tensile speed of 300 mm / min to the 180° peel bond strength to the glass plate at 25°C and a tensile speed of 300 mm / min (180° peel bond strength to the glass plate at 65°C and a tensile speed of 300 mm / min / 180° peel bond strength to the glass plate at 25°C and a tensile speed of 300 mm / min × 100) is 30 or more. Since the elastic modulus of the adhesive layer decreases at high temperatures, the above ratio usually becomes smaller, but the above ratio of the adhesive sheet of the first aspect of the present invention is 30 or more, therefore, the adhesive strength at high temperatures, the bonding reliability, and the suppression of lift-off in height differences are superior.
[0032] From the viewpoint of achieving sufficient adhesion on a transparent conductive film with a metal wiring layer formed on a metal mesh film, silver nanowire film, or the like, the adhesive sheet of the first aspect of the present invention preferably has a 10 N / 20 mm or more peel adhesion force on a glass plate at 25°C and a tensile speed of 300 mm / min at 180°.
[0033] In the first aspect of the present invention, the gelation rate of the aforementioned adhesive layer is preferably 40 to 85% from the viewpoint of maintaining excellent adhesion at high temperatures, adhesive reliability, and achieving excellent flexibility.
[0034] From the viewpoint of excellent transparency and appearance, the adhesive sheet of the first aspect of the present invention preferably has a haze (according to JISK7136) of 1.0% or less.
[0035] From the viewpoint of excellent transparency and appearance, the adhesive sheet of the first aspect of the present invention preferably has a total light transmittance (according to JIS K7361-1) of 90% or more.
[0036] From the viewpoint of minimizing peeling at areas with height differences and maintaining an excellent appearance, the thickness of the adhesive sheet in the first aspect of the present invention is preferably 12 to 350 μm.
[0037] In the first aspect of the present invention, the number average molecular weight (Mn) of the hydrogenated polyolefin resin (B) is preferably 1000 to 5000. This configuration is preferred in that it imparts appropriate stress relief and flowability to the aforementioned adhesive layer and improves compatibility with the acrylic polymer (A). That is, a configuration with a number average molecular weight (Mn) of 1000 or more is preferred in that it can impart appropriate stress relief and flowability to the aforementioned adhesive layer. In addition, a configuration with a number average molecular weight (Mn) of 5000 or less is preferred in that it can improve compatibility with the acrylic polymer (A) and maintain the transparency of the aforementioned adhesive layer to a higher degree.
[0038] In the first aspect of the present invention, the polydispersity (Mw / Mn) of the hydrogenated polyolefin resin (B) is preferably 2.0 or less. This configuration is preferred in that it imparts appropriate stress relief and flowability to the aforementioned adhesive layer and improves compatibility with the acrylic polymer (A).
[0039] In a first aspect of the present invention, the hydrogenated polyolefin resin (B) preferably contains at least one selected from the group consisting of hydrogenated polyolefins and hydrogenated polyolefin polyols. This configuration is preferred in that it can further enhance the aforementioned effects of the hydrogenated polyolefin resin (B) that can form an adhesive layer with low dielectric constant, good adhesion at high temperatures, high adhesion reliability, and excellent height difference followability.
[0040] In a first aspect of the present invention, the hydrogenated polyolefin resin (B) preferably comprises at least one selected from the group consisting of hydrogenated polybutadiene and hydrogenated polybutadiene polyol. This configuration is preferred in that it can further enhance the aforementioned effects of the hydrogenated polyolefin resin (B) that can form an adhesive layer with low dielectric constant, good adhesion at high temperatures, high adhesion reliability, and excellent height difference followability.
[0041] In the first aspect of the present invention, the aforementioned adhesive layer preferably comprises 3 to 35 parts by weight of the aforementioned hydrogenated polyolefin resin (B) relative to 100 parts by weight of the acrylic polymer (A). This configuration is preferred from the viewpoint of imparting appropriate stress relief, flowability, excellent height difference absorption, adhesion, and processability to the aforementioned adhesive layer. That is, a configuration in which the content of hydrogenated polyolefin resin (B) is 3 parts by weight or more is preferred in terms of imparting excellent height difference absorption to the aforementioned adhesive layer. In addition, a configuration in which the content is 35 parts by weight or less is preferred in terms of improving the gelation rate of the aforementioned adhesive layer, maintaining high adhesion strength at high temperatures, and bonding reliability. Furthermore, it is also preferred in terms of improving processability by preventing process contamination caused by stains at the cut ends of the adhesive layer.
[0042] In the first aspect of the present invention, the acrylic polymer (A) preferably comprises an alkyl (meth)acrylate having a branched alkyl group having 10 to 24 carbon atoms as a constituent monomer component. In this application specification, the term "alkyl (meth)acrylate having a branched alkyl group having 10 to 24 carbon atoms" is sometimes referred to as "alkyl (meth)acrylate (A)".
[0043] Alkyl methacrylate (A) is a monomer component with low polarity. Therefore, when an acrylic polymer (A) contains alkyl methacrylate (A) as a constituent monomer component, it becomes a polymer with a low dielectric constant, enabling the creation of an adhesive layer with a low dielectric constant. Therefore, it is preferable to prevent malfunctions caused by ion migration, even when bonding films with metal wiring, such as metal mesh films or silver nanowire films.
[0044] In the first aspect of the present invention, the (meth)acrylate alkyl ester (A) (an (meth)acrylate alkyl ester having branched alkyl groups having 10 to 24 carbon atoms) preferably comprises (meth)acrylate isostearate. This configuration is preferred in that it is easy to control the dielectric constant of the acrylic polymer (A) to be low. In addition, this configuration is also preferred in that it further improves the compatibility with the hydrogenated polyolefin resin (B), thereby enabling a higher degree of maintenance of the transparency of the aforementioned adhesive layer.
[0045] In the first aspect of the present invention, it is preferred that the content of alkyl methacrylate (A) (an alkyl methacrylate having a branched alkyl group having 10 to 24 carbon atoms) is 3 to 50 parts by weight relative to the total amount (100 parts by weight) of the monomer components constituting the acrylic polymer (A). This configuration is preferred in that it imparts a suitable dielectric constant to the acrylic polymer (A) and compatibility with the hydrogenated polyolefin resin (B). That is, a configuration in which the content of alkyl methacrylate (A) is 3 parts by weight or more is preferred in that it imparts a low dielectric constant to the acrylic polymer (A) and compatibility with the hydrogenated polyolefin resin (B). In addition, a configuration in which the content is 50 parts by weight or less is preferred in that it provides suitable stress relief and excellent height difference absorption in the aforementioned adhesive layer.
[0046] In a first aspect of the present invention, it is preferred that the monomer component constituting the acrylic polymer (A) further comprises at least one alkyl (meth)acrylate selected from the group consisting of a straight-chain alkyl group having 1 to 24 carbon atoms and a branched alkyl (meth)acrylate having 3 to 9 carbon atoms. This configuration is preferred in that it can adjust the Tg of the acrylic polymer (A) itself, improve the stress relief of the aforementioned adhesive layer, and improve the height difference tracking performance. Furthermore, in order to further improve the compatibility with the hydrogenated polyolefin resin (B) and thereby maintain the transparency of the aforementioned adhesive layer to a higher degree, the monomer component preferably is an alkyl (meth)acrylate having a straight-chain alkyl group having 1 to 24 carbon atoms.
[0047] In the first aspect of the present invention, it is preferable that the hydroxyl-containing monomer contains 0.1 to 25 parts by weight relative to the total amount (100 parts by weight) of monomer components constituting the acrylic polymer (A). This configuration is preferred in terms of imparting good cohesive strength, high high-temperature bonding reliability, and good compatibility with the hydrogenated polyolefin resin (B) to the aforementioned adhesive layer. That is, a configuration in which the content of hydroxyl-containing monomer is 0.1 parts by weight or more is preferred in terms of imparting good cohesive strength and high bonding reliability to the aforementioned adhesive layer. In addition, a configuration in which the content is 25 parts by weight or less is preferred in terms of obtaining good compatibility with the hydrogenated polyolefin resin (B).
[0048] In the first aspect of the present invention, it is preferred that the monomer composition (100 parts by weight) of the acrylic polymer (A) contains 3 to 30 parts by weight of at least one monomer selected from nitrogen-containing monomers and alicyclic monomers. This composition is preferred in that it imparts good cohesive strength to the aforementioned adhesive layer, high high-temperature bonding reliability, and good compatibility with the hydrogenated polyolefin resin (B). That is, a composition in which the content of at least one monomer selected from nitrogen-containing monomers and alicyclic monomers is 3 parts by weight or more is preferred in that it imparts good cohesive strength to the aforementioned adhesive layer and high bonding reliability. In addition, a composition in which the content is 30 parts by weight or less is preferred in that it obtains good compatibility with the hydrogenated polyolefin resin (B).
[0049] In the first aspect of the present invention, it is preferable that the acrylic polymer (A) does not contain or substantially does not contain carboxyl-containing monomers as constituent monomer components. This configuration is preferred in that it can provide excellent corrosion protection for metal wiring such as metal mesh wiring and silver nanowire layers.
[0050] In the first aspect of the invention, the aforementioned adhesive layer preferably further contains a polyfunctional (meth)acrylate. This configuration is preferred in that the aforementioned adhesive layer has moderate cohesive strength, easily improves adhesion, and exhibits high absorbency.
[0051] In the first aspect of the present invention, the aforementioned adhesive layer preferably further contains a rust inhibitor. This configuration is preferred in that it can achieve excellent anti-corrosion effects on metal wiring such as metal mesh wiring and silver nanowire layers. The rust inhibitor is preferably a benzotriazole compound in terms of compatibility with the acrylic polymer (A), transparency, and, more importantly, in that it does not easily hinder the reaction (crosslinking, polymerization) of the acrylic polymer (A) after its addition.
[0052] In the first aspect of the invention, the aforementioned adhesive layer preferably further contains a silane coupling agent. This configuration is preferred in that it readily yields excellent adhesion to glass (especially excellent adhesion reliability to glass under high temperature and humidity).
[0053] In the first aspect of the present invention, the aforementioned adhesive layer preferably further contains an antioxidant. This configuration is preferred in preventing the adhesive sheet of the first aspect of the present invention from oxidizing and deteriorating during storage.
[0054] A second aspect of the present invention provides an optical component having at least an adhesive sheet and a substrate as described in the first aspect of the present invention, wherein the substrate has metal wiring on at least one side, and the adhesive sheet is attached to the side of the substrate having the metal wiring.
[0055] Furthermore, a third aspect of the present invention provides a touch panel having at least an adhesive sheet and a substrate as described in the first aspect of the present invention, wherein the substrate has metal wiring on at least one side, and the adhesive sheet is attached to the side of the substrate having the metal wiring.
[0056] In the optical component of the second aspect of the present invention and the touch panel of the third aspect of the present invention, the aforementioned metal wiring is preferably metal mesh wiring or silver nanowires.
[0057] The optical component of the second aspect of the present invention and the touch panel of the third aspect of the present invention utilize an adhesive sheet with low dielectric constant, good adhesion at high temperatures, high adhesion reliability, and excellent height difference tracking to be attached to metal wiring such as metal mesh wiring or silver nanowires. Therefore, the adhesive sheet fills the height difference of the metal wiring without gaps and is less prone to malfunction.
[0058] The effects of the invention
[0059] The adhesive sheet of the present invention has an adhesive layer with low dielectric constant, good adhesion at high temperatures, high adhesion reliability, and excellent height difference tracking. Therefore, by using the adhesive sheet of the present invention to bond metal mesh films and silver nanowire films, it is possible to effectively manufacture high-performance optical components such as touch panels that maintain adhesion at high temperatures, have good adhesion reliability, exhibit excellent height difference absorption with sufficient height difference tracking to avoid residual air bubbles, and are less prone to malfunction.
[0060] Therefore, the adhesive sheet of the present invention is preferably used for attaching to optical components having metal mesh wiring, silver nanowire layers, and especially for transparent conductive films having metal wiring layers such as metal mesh films and silver nanowire films. Attached Figure Description
[0061] Figure 1 A schematic diagram illustrating a preferred embodiment of the optical component of the present invention.
[0062] Figure 2 A schematic diagram illustrating a preferred embodiment of the touch panel of the present invention.
[0063] Figure 3 This is a top view of the glass with a height difference used in the evaluation of foaming resistance and peeling properties.
[0064] Figure 4 This is a cross-sectional view of the glass with the height difference mentioned above (cross-sectional view along line A-A').
[0065] Figure 5 This is a cross-sectional view of the glass with the height difference mentioned above (cross-sectional view along line B-B'). Detailed Implementation
[0066] [1. Adhesive sheet and adhesive layer]
[0067] The adhesive sheet of the first aspect of the present invention is an adhesive sheet having an adhesive layer, wherein the adhesive layer comprises an acrylic polymer (A) and a hydrogenated polyolefin resin (B).
[0068] The dielectric constant of the aforementioned adhesive layer at a frequency of 1 MHz is 2.3–3.5.
[0069] The aforementioned adhesive sheet exhibits a 180° peel bond strength of over 6 N / 20 mm to the glass plate at 65°C and a tensile speed of 300 mm / min.
[0070] The ratio of the aforementioned adhesive sheet's 180° peel bond strength to the glass plate at 65°C and a tensile speed of 300 mm / min to its 180° peel bond strength to the glass plate at 25°C and a tensile speed of 300 mm / min (180° peel bond strength to the glass plate at 65°C and a tensile speed of 300 mm / min / 180° peel bond strength to the glass plate at 25°C and a tensile speed of 300 mm / min × 100) is 30 or more.
[0071] In this specification, the adhesive layer constituting the adhesive sheet of the first aspect of the present invention is sometimes referred to as "the adhesive layer of the present invention". Additionally, the adhesive composition forming the adhesive layer of the present invention is sometimes referred to as "the adhesive composition of the present invention".
[0072] Furthermore, for example, the case of "the adhesive layer of the present invention contains an acrylic polymer (A) and a hydrogenated polyolefin resin (B)" also includes the case where the adhesive composition forming the adhesive layer of the present invention (the adhesive composition of the present invention) contains an acrylic polymer (A) and a hydrogenated polyolefin resin (B). The same applies to cases where the adhesive layer of the present invention contains components other than the acrylic polymer (A) and the hydrogenated polyolefin resin (B), or where it does not contain or substantially does not contain these components.
[0073] In addition to the above-described components, the adhesive layer of the present invention (the adhesive composition of the present invention) may also contain polyfunctional (meth)acrylates, rust inhibitors, silane coupling agents, antioxidants, and other additives, as described below.
[0074] The adhesive composition of the present invention can have any form, for example, emulsion type, hot melt type, solvent-free type (active energy ray curing type, such as monomer mixture, or monomer mixture and a portion thereof, etc.). In particular, the adhesive composition of the present invention is preferably not solvent-based. This is because if an adhesive layer is obtained from a solvent-based adhesive composition, undesirable appearance such as grapefruit peel is easily produced. It should be noted that "grapefruit peel" refers to the unevenness of the peel of a "grapefruit," a type of citrus fruit. Furthermore, from the viewpoint of obtaining an adhesive layer with excellent appearance, the adhesive composition of the present invention is preferably active energy ray curing type. In this specification, adhesive composition refers to a composition for forming an adhesive layer, including the meaning of a composition for forming an adhesive.
[0075] The adhesive composition of the present invention, as described above, is preferably not solvent-based, that is, preferably does not contain or substantially does not contain organic solvents.
[0076] The organic solvents mentioned above are not particularly limited to any organic compound used as a solvent. Examples include hydrocarbon solvents such as cyclohexane, hexane, and heptane; aromatic solvents such as toluene and xylene; ester solvents such as ethyl acetate and methyl acetate; ketone solvents such as acetone and methyl ethyl ketone; and alcohol solvents such as methanol, ethanol, butanol, and isopropanol. It should be noted that the organic solvents mentioned above can be mixtures containing two or more organic solvents.
[0077] In the adhesive composition of the present invention, "substantially free" organic solvent means that, except where organic solvent is inevitably mixed in, no organic solvent is actively mixed in. Specifically, when the content of organic solvent in the adhesive composition is 1.0% by weight or less (preferably 0.5% by weight or less, more preferably 0.2% by weight or less) relative to the total amount of the adhesive composition (total weight, 100% by weight), it can be said to be substantially free.
[0078] The base polymer constituting the adhesive composition of the present invention includes acrylic polymers, taking into account aspects such as transparency, weather resistance, adhesive reliability, and the ease of functional design of the adhesive layer due to the wide variety of monomers. That is, the adhesive composition of the present invention is an acrylic adhesive composition containing the acrylic polymer (A) described later as a base polymer. It should be noted that acrylic polymer (A) can be used alone or in combination of two or more types.
[0079] The content of the acrylic polymer (A) as the base polymer in the adhesive composition of the present invention is not particularly limited, but is preferably 74% by weight or more (e.g., 74 to 99.9% by weight), more preferably 84% by weight or more (e.g., 84 to 99.9% by weight).
[0080] In the adhesive layer (adhesive composition of the present invention), the monomer component constituting the acrylic polymer (A) preferably does not contain or substantially does not contain carboxyl-containing monomers. Therefore, the adhesive layer can provide corrosion protection against metal wiring such as metal mesh wiring and silver nanowires. The content of carboxyl-containing monomers relative to the total amount of the adhesive layer is preferably 0.05% by weight or less (e.g., 0 to 0.05% by weight), more preferably 0.01% by weight or less (e.g., 0 to 0.01% by weight), and even more preferably 0.001% by weight or less (e.g., 0 to 0.001% by weight), which is substantially negligible.
[0081] The dielectric constant of the adhesive layer of the present invention is controlled to be low, which can prevent malfunctions of optical components such as touch panels having the adhesive layer. The dielectric constant of the adhesive layer of the present invention at a frequency of 1 MHz is 3.5 or less, preferably 3.3 or less, and more preferably 3.2 or less. The lower limit value of the dielectric constant at a frequency of 1 MHz is not particularly limited, but it is preferably 2.3 or more, more preferably 2.4 or more, and even more preferably 2.5 or more.
[0082] Furthermore, the dielectric constant at a frequency of 100 kHz is preferably 4.0 or less, more preferably 3.9 or less, and even more preferably 3.8 or less. The lower limit of the dielectric constant at a frequency of 100 kHz is not particularly limited, but is preferably 2.3 or more, more preferably 2.4 or more, and even more preferably 2.5 or more.
[0083] The dielectric constant of the adhesive layer of the present invention can be adjusted by modifying the monomer composition of the acrylic polymer (A), the type of hydrogenated polyolefin resin (B), and the mixing ratio of the acrylic polymer (A) and the hydrogenated polyolefin resin (B). The dielectric constant is determined by the method described in the examples below.
[0084] The adhesive sheet of the present invention exhibits excellent adhesion strength and bonding reliability at high temperatures. Its 180° peel adhesion strength to a glass plate at 65°C and a tensile speed of 300 mm / min (particularly the 180° peel adhesion strength of the adhesive surface provided by the adhesive layer (the adhesive layer of the present invention) to the glass plate at 65°C and a tensile speed of 300 mm / min) is 6 N / 20 mm or more, preferably 6.5 N / 20 mm or more, more preferably 7 N / 20 mm or more, and even more preferably 7.5 N / 20 mm or more. Because the adhesive sheet of the present invention provides a certain or higher 180° peel adhesion strength to a glass plate at 65°C and a tensile speed of 300 mm / min, it offers superior adhesion to glass at high temperatures and better suppression of lift-off due to height differences. It should be noted that the adhesive sheet of the present invention does not particularly limit the upper limit of the 180° peel adhesion force of the glass plate at 65°C and a tensile speed of 300 mm / min. For example, it is preferred to be 60 N / 20 mm or less, and more preferably 40 N / 20 mm or less.
[0085] Furthermore, the ratio of the 180° peel bond strength of the adhesive sheet of the present invention to the glass plate at 65°C and a tensile speed of 300 mm / min to the 180° peel bond strength of the adhesive sheet to the glass plate at 25°C and a tensile speed of 300 mm / min (180° peel bond strength of the adhesive sheet to the glass plate at 65°C and a tensile speed of 300 mm / min / 180° peel bond strength of the adhesive sheet to the glass plate at 25°C and a tensile speed of 300 mm / min × 100) is 30 or more, more preferably 35 or more, further preferably 40 or more, and even more preferably 45 or more. Since the elastic modulus of the adhesive layer decreases at high temperatures, the above ratio usually decreases, but the above ratio of the adhesive sheet of the present invention is a certain value or higher, thus providing superior adhesion strength, adhesion reliability, and suppression of lift-off in height differences at high temperatures. The upper limit of the above ratio is not particularly limited, and practically it can be 100 or less, or 95 or less.
[0086] The adhesive sheet of the present invention does not have a particularly limited 180° peel adhesion force to the glass plate at 25°C and a tensile speed of 300 mm / min (especially the 180° peel adhesion force of the adhesive surface provided by the adhesive layer (the adhesive layer of the present invention) to the glass plate at 25°C and a tensile speed of 300 mm / min). From the viewpoint that a high adhesion force results in sufficient adhesion to metal surfaces such as metal mesh wiring and silver nanowires, and also improves the corrosion resistance, it is preferably 10 N / 20 mm or more, more preferably 12 N / 20 mm or more, further preferably 14 N / 20 mm or more, and even more preferably 16 N / 20 mm or more. When the adhesive sheet of the present invention has a certain or higher 180° peel adhesion force to the glass plate at 25°C and a tensile speed of 300 mm / min, the adhesion to the glass and the suppression of lifting due to height differences are even more excellent. It should be noted that the adhesive sheet of the present invention does not particularly limit the upper limit of the 180° peel adhesion force of the glass plate at 25°C and a tensile speed of 300 mm / min. For example, it is preferred to be 60 N / 20 mm or less, and more preferably 40 N / 20 mm or less.
[0087] The 180° peel bond strength of the glass plate at 25°C and 65°C and a tensile speed of 300 mm / min was determined by the following method for measuring 180° peel bond strength. There are no particular limitations on the glass plate mentioned above; for example, the trade name "Soda-lime Glass #0050" (manufactured by Matsunami Glass Industry Co., Ltd.) can be cited. Alkali-free glass and chemically strengthened glass can also be cited.
[0088] The adhesive strength and adhesive strength ratio of the adhesive sheet of the present invention can be adjusted by adjusting the monomer composition of the acrylic polymer (A), the type of hydrogenated polyolefin resin (B), and the mixing ratio of the acrylic polymer (A) and the hydrogenated polyolefin resin (B).
[0089] (A-1. Method for determining 180° peel adhesion)
[0090] The adhesive surface of the adhesive sheet is attached to the substrate and pressed using a 2kg roller with one round trip. The mixture is then cured for 30 minutes at 23°C and 50% RH. After curing, according to JIS Z 0237, the adhesive sheet is peeled from the substrate at 25°C or 65°C, 50% RH, a tensile speed of 300 mm / min, and a peel angle of 180°. The 180° peel bond strength (N / 20mm) is measured.
[0091] The gel ratio (proportion of solvent-insoluble components) of the adhesive layer of the present invention is preferably 40-85%, more preferably 45-80%, and even more preferably 45-75%. When the gel ratio is 40% or higher, the cohesive strength of the adhesive layer is improved, foaming and peeling at the interface with the adhered object under high temperature conditions are suppressed, and excellent foaming and peeling resistance is easily obtained, which is preferred. Furthermore, from the viewpoint of changes in the appearance of the roll during long-term storage in roll form and the ease of processing when treated as a sheet, it is preferred. Additionally, from the viewpoint of imparting softness to the adhesive layer and improving flexibility, it is also preferred. It should be noted that when the gel ratio is 95% or lower, moderate softness is obtained, and adhesion is further improved, which is preferred.
[0092] (Gel ratio)
[0093] Specifically, the gel ratio (the proportion of solvent-insoluble components) mentioned above is, for example, a value calculated by the following "Method for Determining Gel Ratio".
[0094] Take approximately 0.1g of the adhesive layer from the adhesive sheet, wrap it with a porous tetrafluoroethylene sheet (trade name "NTF1122", manufactured by Nitto Denko Corporation) with an average pore size of 0.2μm, and then tie it with kite string. Measure the weight at this point, and use this weight as the weight before impregnation. It should be noted that this weight before impregnation is the total weight of the adhesive layer (the adhesive layer taken above), the tetrafluoroethylene sheet, and the kite string. In addition, the combined weight of the tetrafluoroethylene sheet and the kite string is also measured beforehand, and this weight is used as the bag weight.
[0095] Next, the object (referred to as the "sample"), which was made by wrapping the adhesive layer with a tetrafluoroethylene sheet and binding it with kite string, was placed in a 50 ml container filled with ethyl acetate and left to stand at 23°C for 7 days. Then, the sample (after ethyl acetate treatment) was removed from the container, transferred to an aluminum cup, and dried at 130°C in a desiccator for 2 hours to remove the ethyl acetate. The weight was then measured and recorded as the weight after impregnation.
[0096] Then, the gel ratio is calculated according to the following formula.
[0097] Gel yield [% (weight %)] = (XY) / (ZY) × 100
[0098] It should be noted that the aforementioned gel rate can be controlled, for example, by the monomer composition of the acrylic polymer (A), the weight-average molecular weight, and the amount (addition amount) of the crosslinking agent. Furthermore, when the adhesive composition of the present invention is cured by ultraviolet irradiation, the carbon-carbon double bonds in the hydrogenated polyolefin resin (B) decrease, thus reducing the likelihood of polymerization inhibition and preventing a decrease in the gel rate.
[0099] The adhesive sheet of the present invention exhibits excellent transparency due to the excellent compatibility between the acrylic polymer (A) and the hydrogenated polyolefin resin (B). Therefore, the visual visibility and appearance of the adhesive sheet are excellent. Thus, the adhesive sheet of the present invention is suitable for optical applications.
[0100] The haze of the adhesive sheet of the present invention (according to JIS K7136) is not particularly limited, but preferably 1.0% or less, more preferably 0.8% or less. A haze of 1.0% or less provides excellent transparency and a superior appearance, and is therefore preferred. The lower limit of the haze is not particularly limited; theoretically it is 0%, but practically it can be 0.01% or more. It should be noted that, for the above-mentioned haze, for example, after the adhesive sheet has been left to stand at normal temperature (23°C, 50% RH) for at least 24 hours, it is peeled off when it has an isolator, adhered to a glass slide (e.g., a glass slide with 92% total transmittance and 0.2% haze), and the resulting object is used as a sample for measurement using a haze meter (manufactured by Murakami Color Technology Research Institute Co., Ltd., trade name "HM-150N") or its equivalent.
[0101] The total transmittance (according to JIS K7361-1) of the adhesive sheet in the visible light wavelength region of the present invention is not particularly limited, but preferably 90% or more, more preferably 91% or more, and even more preferably 92% or more. A total transmittance of 90% or more provides excellent transparency and a superior appearance, and is therefore preferred. The upper limit of the total transmittance is not particularly limited; theoretically, it is the value obtained by subtracting the light loss (Fresnel loss) caused by reflection at the air interface from 100%, and practically, it can be 95% or less. It should be noted that, for the above-mentioned total transmittance, for example, after the adhesive sheet has been left to stand at normal temperature (23°C, 50% RH) for at least 24 hours, it is peeled off with an isolator and bonded to a glass slide (e.g., a glass slide with a total transmittance of 92% and a haze of 0.2%). The resulting object is used as a sample and measured using a haze meter (manufactured by Murakami Color Technology Research Institute Co., Ltd., trade name "HM-150N") or its equivalent.
[0102] The thickness (total thickness) of the adhesive sheet of the present invention is not particularly limited, but is preferably 12 to 350 μm, more preferably 12 to 300 μm. A thickness of a certain value or higher is preferred as it reduces the likelihood of peeling at height difference areas. Furthermore, a thickness of a certain value or lower is preferred because it facilitates maintaining an excellent appearance during manufacturing and storage, and reduces the likelihood of adhesive residue buildup during cutting. It should be noted that the thickness of the adhesive sheet of the present invention does not include the thickness of the separator.
[0103] There are no particular limitations on the method for manufacturing the adhesive sheet with an adhesive layer according to the present invention. For example, it can be manufactured by preparing the adhesive composition (precursor composition) of the present invention, irradiating it with active energy rays as needed, heating and drying it, etc. Specifically, examples include: manufacturing it by adding hydrogenated polyolefin resin (B) to a mixture of monomer components or a portion thereof, adding other additives as needed, etc.
[0104] [1-1. Acrylic polymers (A)]
[0105] The adhesive layer of the present invention is an acrylic adhesive layer with an acrylic polymer (A) as the main component. The specific content of the acrylic polymer (A) is not particularly limited, but it is preferably 74% by weight or more (e.g., 74 to 99.9% by weight), more preferably 84% by weight or more (e.g., 84 to 99.9% by weight), relative to the total amount of the adhesive layer of the present invention (total weight, 100% by weight).
[0106] The adhesive composition of the present invention, which forms an adhesive layer containing an acrylic polymer (A) as the main component, is not particularly limited. Examples include compositions in which the acrylic polymer (A) is an essential component; compositions in which a mixture of monomer components constituting the acrylic polymer (A) (sometimes referred to as a "monomer mixture") or a portion thereof is an essential component. There is no particular limitation; examples of the former include so-called water-dispersible compositions (emulsion compositions), and examples of the latter include so-called active energy ray-cured compositions. It should be noted that the above-described adhesive compositions may contain other additives as needed.
[0107] The aforementioned "monomer mixture" includes cases consisting of a single monomer component and cases consisting of two or more monomer components. Furthermore, the aforementioned "partial polymer" refers to a composition in which one or more components of the aforementioned monomer mixture have undergone partial polymerization. Preferably, the aforementioned adhesive composition includes a monomer mixture or its partial polymer as an essential component.
[0108] Acrylic polymer (A) is a polymer that contains acrylic monomers (acrylic monomers) as essential monomer units (monomer units, monomer structural units). In other words, acrylic polymer (A) is a polymer that contains structural units derived from acrylic monomers as structural units. That is, acrylic polymer (A) is a polymer constructed (formed) by using acrylic monomers as essential monomer components. It should be noted that in this specification, "(meth)acrylic acid" means either or both of "acrylic acid" and "methacrylate," and the same applies to others. The weight-average molecular weight of acrylic polymer (A) is not particularly limited, but is preferably 100,000 to 5,000,000.
[0109] The acrylic polymer (A) is preferably a polymer containing alkyl (meth)acrylate (A) (an alkyl (meth)acrylate having branched alkyl groups having 10 to 24 carbon atoms). That is, the acrylic polymer (A) of the present invention is preferably obtained by polymerizing a monomer component containing an alkyl (meth)acrylate having long-chain branched alkyl groups such as alkyl (meth)acrylate (A). Utilizing the aforementioned long-chain branched alkyl group, an adhesive layer with a low dielectric constant can be achieved. Even when attached to a transparent conductive film with a metal wiring layer such as a metal mesh or silver nanowire, the dielectric constant of the adhesive layer remains low, thus preventing malfunctions.
[0110] To reduce the dielectric constant, according to the Clausius-Mossotti equation, it is considered that the dipole moment of the molecules can be reduced, thereby increasing the molar volume. The main monomer unit of the acrylic polymer (A) of the present invention, which constitutes the main component of the adhesive layer of the present invention, involves an alkyl (meth)acrylate (A) with long-chain branched alkyl groups. It is believed that the molar volume of the adhesive layer obtained from the adhesive composition of the present invention increases, and since the alkyl groups are branched, the dipole moment decreases. It is considered that by using the acrylic polymer (A) of the present invention with branched alkyl groups having 10 to 24 carbon atoms as the alkyl group, an adhesive layer with a balance between increased molar volume and decreased dipole moment can be obtained.
[0111] The Tg of homopolymers of (meth)acrylate alkyl esters (A) ((meth)acrylate alkyl esters having branched alkyl groups with 10 to 24 carbon atoms) is preferably -80 to 0°C, and more preferably -70 to -10°C. When the Tg of the homopolymer is below -80°C, the elastic modulus of the adhesive layer at room temperature may decrease excessively, which is not preferred; when it exceeds 0°C, the adhesive strength may decrease, which is also not preferred. The Tg of the homopolymer is a value measured using a differential scanning calorimeter (DSC). In addition, the branched alkyl group is preferably 10 to 24 carbon atoms from the perspective of satisfying a low dielectric constant and a moderate elastic modulus, but the (meth)acrylate alkyl ester having the preferred alkyl group can be suitably selected according to the manufacturing method of the (meth)acrylate polymer. For example, when manufacturing (meth)acrylate polymers by solution polymerization, the aforementioned alkyl group is preferably 10 to 18 carbon atoms, more preferably 10 to 16 carbon atoms, and more preferably 10 to 14 carbon atoms. When acrylic polymers (A) are manufactured by radiation polymerization or the like, the aforementioned alkyl group preferably has 12 to 18 carbon atoms, and more preferably 14 to 18 carbon atoms. It should be noted that even if the Tg of the homopolymer of (meth)acrylate alkyl ester is -80 to 0°C, the effect of lowering the dielectric constant of the adhesive layer is not significant when the alkyl group is linear or has 9 or fewer carbon atoms.
[0112] Examples of (meth)acrylate alkyl esters (A) include, for example, isodecanyl acrylate (10 carbons, Tg = -60°C for homopolymer, hereinafter abbreviated as Tg), isodecanyl methacrylate (10 carbons, Tg = -41°C), isomyrmyristyl acrylate (14 carbons, Tg = -56°C), isostearyl acrylate (18 carbons, Tg = -18°C), 2-propylpentyl acrylate, isoundecyl acrylate, isododecyl acrylate, isotridecyl acrylate, isopentadecanyl acrylate, isohexadecyl acrylate, isoheptadecyl acrylate, and the aforementioned methacrylate monomers. Alkyl acrylate (A) can be used alone or in combination of two or more.
[0113] Furthermore, among the aforementioned branched alkyl groups having 10 to 24 carbon atoms, those having a tert-butyl or similar branched alkyl group at the end of the ester group are particularly preferred, especially considering the resulting adhesive layer with an increased molar volume and a decreased dipole moment, thus achieving a balance between both. Additionally, the excellent compatibility between the acrylic polymer (A) and the hydrogenated polyolefin resin (B) of the present invention is also preferred. As the branched alkyl group at the end of the ester group, branched alkyl groups having 4 to 6 carbon atoms, such as tert-butyl, neopentyl, or tert-pentyl, are preferred, with tert-butyl being particularly preferred. As a preferred example of an alkyl (meth)acrylate (A) having a tert-butyl group at the end of the ester group, isostearyl acrylate as shown in the following formula can be cited.
[0114]
[0115] Furthermore, regarding the alkyl methacrylate (A), alkyl methacrylate is more preferable than alkyl acrylate in terms of the effect of increasing the molar volume and decreasing the dipole moment to achieve a lower dielectric constant in the adhesive layer. On the other hand, alkyl acrylate is more preferable than alkyl methacrylate in terms of shortening the polymerization time of the acrylic polymer (A) and thus improving productivity. In particular, alkyl acrylate is suitable when the acrylic polymer (A) of the present invention is cured by radiation polymerization.
[0116] The content (proportion) of the aforementioned (meth)acrylate alkyl ester (A) in all monomer units (total monomer components constituting acrylic polymer (A)) is not particularly limited, but is preferably 3 to 50 parts by weight, more preferably 10 to 48 parts by weight, and even more preferably 20 to 45 parts by weight relative to the total monomer components constituting acrylic polymer (A) (100 parts by weight). Using 3 parts by weight or more is preferred in terms of lower dielectric constant, and using 50% by weight or less is preferred in terms of maintaining adhesive strength and height difference followability.
[0117] The acrylic polymer (A) of the present invention may contain alkyl methacrylates (hereinafter, sometimes referred to as "alkyl methacrylate (B)") other than alkyl methacrylate (A) as monomer components. Alkyl methacrylate (A) is a monomer component with a high Tg in homopolymers. Therefore, by making the acrylic polymer (A) also contain alkyl methacrylate (B) whose Tg in homopolymers is lower than that in alkyl methacrylate (A), it is possible to adjust the Tg of the acrylic polymer (A) itself, improve the stress relief of the adhesive layer of the present invention, and improve the height difference tracking.
[0118] Examples of the aforementioned alkyl methacrylate (B) include alkyl methacrylates having linear alkyl groups with 1 to 24 carbon atoms and alkyl methacrylates having branched alkyl groups with 3 to 9 carbon atoms. From the perspective of further improving compatibility with hydrogenated polyolefin resin (B) and thus maintaining the transparency of the adhesive layer of the present invention more effectively, alkyl methacrylates having linear alkyl groups with 1 to 24 carbon atoms are preferred. Alkyl methacrylate (B) can be used alone or in combination of two or more types.
[0119] Examples of alkyl (meth)acrylates having a straight-chain alkyl group having 1 to 24 carbon atoms include methyl (meth)acrylate, ethyl (meth)acrylate, propyl (meth)acrylate, butyl (meth)acrylate (n-butyl meth)acrylate, pentyl (meth)acrylate, hexyl (meth)acrylate, pentyl (meth)acrylate, octyl (meth)acrylate, nonyl (meth)acrylate, decyl (meth)acrylate, undecyl (meth)acrylate, dodecyl (meth)acrylate, tridecyl (meth)acrylate, tetradecyl (meth)acrylate, pentadecyl (meth)acrylate, hexadecyl (meth)acrylate, heptadecanyl (meth)acrylate, octadecyl (meth)acrylate, nonadecanyl (meth)acrylate, and eicosyl (meth)acrylate.
[0120] Examples of alkyl (meth)acrylates having branched alkyl groups having 3 to 9 carbon atoms include isopropyl (meth)acrylate, isobutyl (meth)acrylate, sec-butyl (meth)acrylate, tert-butyl (meth)acrylate, isoamyl (meth)acrylate, 2-ethylhexyl (meth)acrylate, isooctyl (meth)acrylate, and isononyl (meth)acrylate.
[0121] The Tg of homopolymers of alkyl (meth)acrylate (B) (other than alkyl (meth)acrylates having branched alkyl groups having 10 to 24 carbon atoms) is preferably -100 to -30°C, and more preferably -90 to -40°C. When the Tg of the homopolymer is below -100°C, the elastic modulus of the adhesive layer at room temperature is sometimes excessively reduced, which is not preferred. When the Tg exceeds -30°C, the stress relief of the adhesive layer is sometimes reduced, and the height difference tracking becomes insufficient.
[0122] Among them, as the above-mentioned alkyl (meth)acrylate (B), from the perspective of improving the stress relief of the adhesive layer and thus adjusting the height difference tracking, it is preferable to have a linear alkyl (meth)acrylate having an alkyl group with 6 to 18 carbon atoms, or a branched alkyl (meth)acrylate having 6 to 9 carbon atoms. More preferably, it is preferred to have a linear alkyl (meth)acrylate having an alkyl group with 8 to 14 carbon atoms, or a branched alkyl (meth)acrylate having 7 to 9 carbon atoms. Particularly preferred are 2-ethylhexyl acrylate (branched alkyl group with 8 carbon atoms, Tg = -70°C) and lauryl acrylate (linear alkyl group with 12 carbon atoms, Tg = -50°C).
[0123] Furthermore, regarding alkyl methacrylate (B), from the perspective of increasing the molar volume and decreasing the dipole moment, which results in a lower dielectric constant for the adhesive layer, alkyl methacrylate is more preferred than alkyl acrylate. On the other hand, from the perspective of shortening the polymerization time of the acrylic polymer (A) and thus improving productivity, alkyl acrylate is more preferred than alkyl methacrylate. In particular, when the acrylic polymer (B) of the present invention is cured by radiation polymerization, alkyl acrylate is suitable.
[0124] The content (proportion) of the aforementioned (meth)acrylate alkyl ester (B) in all monomer units (total monomer components constituting acrylic polymer (A)) is not particularly limited, but is preferably 3 to 50 parts by weight, more preferably 10 to 48 parts by weight, and even more preferably 20 to 45 parts by weight relative to the total monomer components constituting acrylic polymer (A) (100 parts by weight). Using 3 parts by weight or more is preferred in terms of maintaining adhesive strength and height difference conformability, and using 50% by weight or less is preferred in terms of reducing dielectric constant.
[0125] In the acrylic polymer (A), in addition to the aforementioned alkyl (meth)acrylate (A) and alkyl (meth)acrylate (B) monomer units, it may also contain copolymerizable monomers (copolymerizable monomers). That is, the acrylic polymer (A) may contain copolymerizable monomers as constituent monomer components. It should be noted that two or more copolymerizable monomers may be used alone or in combination.
[0126] As the aforementioned comonomer, hydroxyl-containing monomers are preferred. If the acrylic polymer (A) contains hydroxyl-containing monomers as monomer units, it is easier to polymerize the constituent monomer components, and good cohesive strength is readily obtained. Therefore, strong adhesion is easily obtained, and the gelation rate is increased, resulting in excellent resistance to foaming and peeling. Furthermore, it is easier to suppress the whitening that sometimes occurs in adhesive sheets under high humidity environments. It should be noted that the rust inhibitors described later are selective in their solubility for monomers; for example, benzotriazole compounds, one of the rust inhibitors described later, have good solubility for hydroxyl-containing monomers.
[0127] The content (ratio) of the hydroxyl-containing monomer relative to the total amount (100 parts by weight) of the monomer components constituting the acrylic polymer (A) is not particularly limited. When the amount of hydroxyl-containing monomer is a certain level or higher, adhesive reliability, such as cohesive strength and foam peel resistance, is easily obtained. The lower limit of the content of the hydroxyl-containing monomer is preferably 0.1 parts by weight or more, more preferably 0.5 parts by weight or more, and even more preferably 1 part by weight or more. In addition, regarding the upper limit of the content of the hydroxyl-containing monomer, from the viewpoint of easily obtaining compatibility with hydrogenated polyolefin resin (B), it is preferably 25 parts by weight or less, more preferably 23 parts by weight or less, and even more preferably 21 parts by weight or less.
[0128] Furthermore, nitrogen-containing monomers and / or alicyclic monomers are preferably used as the aforementioned copolymerizing monomers. If the acrylic polymer (A) contains nitrogen-containing monomers and / or alicyclic monomers as monomer units, moderate cohesive strength is readily obtained. Therefore, increasing the 180° peel bond strength to both the glass and acrylic sheets easily yields strong adhesion; additionally, increasing the gelation rate facilitates excellent foaming peel resistance. Furthermore, moderate flexibility is readily achieved in the adhesive layer, and by adjusting the 300% tensile residual stress to a specific range, excellent stress relief and excellent height difference tracking are readily obtained.
[0129] The content (proportion) of at least one of the nitrogen-containing monomers and alicyclic monomers selected above relative to the total amount (100 parts by weight) of monomer components constituting the acrylic polymer (A) is not particularly limited, but is preferably 3 parts by weight or more. Regarding the lower limit of the content of at least one of the nitrogen-containing monomers and alicyclic monomers selected above, from the perspective of cohesive strength, adhesion, and foam peel resistance, relative to the total amount (100 parts by weight) of monomer components constituting the acrylic polymer (A), it is more preferably 5 parts by weight or more, and even more preferably 10 parts by weight or more. Furthermore, regarding the upper limit of the content of at least one of the nitrogen-containing monomers and alicyclic monomers selected above, from the perspective of more easily obtaining moderate flexibility in the adhesive layer, more easily obtaining excellent stress relief, and excellent height difference tracking, it is preferably 30 parts by weight or less, more preferably 28 parts by weight or less, and even more preferably 25 parts by weight or less.
[0130] The ratio of nitrogen-containing monomers to alicyclic monomers in the acrylic polymer (A) is not particularly limited, and can be appropriately selected from the range of 100 / 0 to 0 / 100, preferably 95 / 5 to 5 / 95, and more preferably 90 / 10 to 10 / 90.
[0131] The aforementioned acrylic polymer (A) can be obtained by polymerizing the monomer units (monomer components) using known and conventional polymerization methods. Examples of polymerization methods for the aforementioned acrylic polymer (A) include solution polymerization, emulsion polymerization, bulk polymerization, and polymerization using active energy rays (active energy ray polymerization). Among these, solution polymerization and active energy ray polymerization are preferred in terms of the transparency, water resistance, and cost of the adhesive layer; more preferably, active energy ray polymerization is preferred.
[0132] Examples of active energy rays used in the above-mentioned active energy ray polymerization (photopolymerization) include ionizing radiation such as alpha rays, beta rays, gamma rays, neutron rays, electron beams, and ultraviolet rays, with ultraviolet rays being particularly preferred. Furthermore, the irradiation energy, irradiation time, and irradiation method of the active energy rays are not particularly limited, as long as they can activate the photopolymerization initiator to cause a reaction of the monomer components.
[0133] Various common solvents can be used in the polymerization of the aforementioned acrylic polymer (A). Examples of such solvents include esters such as ethyl acetate and n-butyl acetate; aromatic hydrocarbons such as toluene and benzene; aliphatic hydrocarbons such as n-hexane and n-heptane; alicyclic hydrocarbons such as cyclohexane and methylcyclohexane; and ketones such as methyl ethyl ketone and methyl isobutyl ketone. It should be noted that two or more solvents can be used alone or in combination.
[0134] Furthermore, during the polymerization of the aforementioned acrylic polymer (A), depending on the type of polymerization reaction, polymerization initiators such as thermal polymerization initiators and photopolymerization initiators (photoinitiators) can be used. It should be noted that polymerization initiators can be used alone or in combination of two or more.
[0135] There are no particular limitations on the aforementioned photopolymerization initiators. Examples include benzoin ether-based photopolymerization initiators, acetophenone-based photopolymerization initiators, α-keto alcohol-based photopolymerization initiators, aromatic sulfonyl chloride-based photopolymerization initiators, photoactive oxime-based photopolymerization initiators, benzoin-based photopolymerization initiators, benzoyl-based photopolymerization initiators, ketal-based photopolymerization initiators, and thioxanone-based photopolymerization initiators. It should be noted that photopolymerization initiators can be used alone or in combination of two or more.
[0136] Examples of benzoin ether-based photopolymerization initiators include, for example, benzoin methyl ether, benzoin ethyl ether, benzoin propyl ether, benzoin isopropyl ether, benzoin isobutyl ether, 2,2-dimethoxy-1,2-diphenylethane-1-one, and anisole methyl ether. Examples of acetophenone-based photopolymerization initiators include, for example, 2,2-diethoxyacetophenone, 2,2-dimethoxy-2-phenylacetophenone, 1-hydroxycyclohexylphenyl ketone, 4-phenoxydichloroacetophenone, and 4-(tert-butyl)dichloroacetophenone. Examples of α-ketool-based photopolymerization initiators include, for example, 2-methyl-2-hydroxyphenylacetone and 1-[4-(2-hydroxyethyl)phenyl]-2-methylpropane-1-one. Examples of aromatic sulfonyl chloride-based photopolymerization initiators include, for example, 2-naphthalenesulfonyl chloride. Examples of photoactive oxime-based photopolymerization initiators include, for example, 1-phenyl-1,1-propanedione-2-(o-ethoxycarbonyl)-oxime. Examples of benzoin-based photopolymerization initiators include, for example, benzoin. Examples of benzoyl-based photopolymerization initiators include, for example, benzoyl. Examples of benzophenone-based photopolymerization initiators include, for example, benzophenone, benzoylbenzoic acid, 3,3'-dimethyl-4-methoxybenzophenone, polyvinylbenzophenone, and α-hydroxycyclohexylphenyl ketone. Examples of ketal-based photopolymerization initiators include, for example, benzoyl dimethyl ketal. Examples of thioxanthone-based photopolymerization initiators include, for example, thioxanthone, 2-chlorothioxanthone, 2-methylthioxanthone, 2,4-dimethylthioxanthone, isopropylthioxanthone, 2,4-diisopropylthioxanthone, and dodecylthioxanthone.
[0137] The amount of the above-mentioned photopolymerization initiator is not particularly limited. For example, it is preferably 0.001 to 1 part by weight, more preferably 0.01 to 0.50 parts by weight, relative to 100 parts by weight of all monomer units of acrylic polymer (A) (the total amount of monomer components constituting acrylic polymer (A)).
[0138] Furthermore, there are no particular limitations on the aforementioned thermal polymerization initiators. Examples include azo polymerization initiators, peroxide polymerization initiators (e.g., benzoyl peroxide, tert-butyl maleate peroxide, etc.), and redox polymerization initiators. Among these, the azo polymerization initiators disclosed in Japanese Patent Application Publication No. 2002-69411 are preferred. Examples of the aforementioned azo polymerization initiators include 2,2'-azobisisobutyronitrile (hereinafter, sometimes referred to as "AIBN"), 2,2'-azobis-2-methylbutyronitrile (hereinafter, sometimes referred to as "AMBN"), 2,2'-azobis(2-methylpropionic acid) dimethyl ester, and 4,4'-azobis-4-cyanovaleric acid.
[0139] The amount of the above-mentioned thermal polymerization initiator is not particularly limited. For example, in the case of the above-mentioned azo polymerization initiator, it is preferably 0.05 to 0.5 parts by weight, more preferably 0.1 to 0.3 parts by weight, relative to 100 parts by weight of all monomer units of acrylic polymer (A) (the total amount of monomer components constituting acrylic polymer (A)).
[0140] [1-2. Monomers containing carboxyl groups, etc.]
[0141] In the adhesive layer of the present invention, the monomer components constituting the acrylic polymer (A) preferably do not substantially contain carboxyl-containing monomers. It should be noted that "substantially not containing" means that, except in cases of unavoidable mixing, they are not actively mixed in. Furthermore, carboxyl-containing monomers refer to monomers having at least one carboxyl group within their molecule. From the viewpoint of obtaining superior anti-corrosion effects, specifically, the content of carboxyl-containing monomers relative to the total amount (100 parts by weight) of the monomer components constituting the acrylic polymer (A) is preferably 0.05 parts by weight or less (e.g., 0 to 0.05 parts by weight), more preferably 0.01 parts by weight or less (e.g., 0 to 0.01 parts by weight), and even more preferably 0.001 parts by weight or less (e.g., 0 to 0.001 parts by weight), which can be considered substantially non-existent. It should be noted that, for example, (meth)acrylic acid, itaconic acid, maleic acid, fumaric acid, crotonic acid, isocrotonic acid, etc. are examples of the above-mentioned carboxyl-containing monomers. In addition, the above-mentioned carboxyl-containing monomers also include anhydride-containing monomers such as maleic anhydride and itaconic anhydride.
[0142] Furthermore, from the viewpoint of obtaining superior anti-corrosion effect, the adhesive layer of the present invention preferably does not substantially contain carboxyl-containing monomers as monomeric components constituting the acrylic polymer (A), nor does it substantially contain monomers having acidic groups other than carboxyl groups (sulfonyl, phosphoric acid, etc.) as monomeric components constituting the acrylic polymer (A). That is, the acrylic polymer (A) preferably does not substantially contain carboxyl-containing monomers or monomers having other acidic groups as its constituent monomeric components. Specifically, the total amount of carboxyl-containing monomers and monomers having other acidic groups constituting the acrylic polymer (A) is preferably 0.05 parts by weight or less (e.g., 0 to 0.05 parts by weight), more preferably 0.01 parts by weight or less (e.g., 0 to 0.01 parts by weight), and even more preferably 0.001 parts by weight or less (e.g., 0 to 0.001 parts by weight) relative to the total amount of monomeric components constituting the acrylic polymer (A) (100 parts by weight), which can be said to be substantially non-existent.
[0143] Furthermore, from the same perspective, the adhesive layer of the present invention preferably does not contain or substantially does not contain monomers containing acidic groups as monomer components constituting polymers other than acrylic polymers (A). For example, it is preferable that it does not substantially contain carboxyl-containing monomers. It should be noted that the meaning of "substantially does not contain," the degree of preference, and monomers having acidic groups other than carboxyl groups, etc., are the same as in the case of monomer components constituting acrylic polymers (A).
[0144] [1-3. Monomers containing basic groups]
[0145] It should be noted that, in the adhesive layer of the present invention, the monomer components constituting the acrylic polymer (A) preferably do not contain or substantially do not contain monomers containing basic groups. Furthermore, for monomer components constituting polymers other than acrylic polymer (A), it is also preferable that they substantially do not contain monomers containing basic groups. This preference for substantially not containing monomers containing basic groups in the adhesive layer, even when not constituting monomer components of various polymers, is the same as in the case of carboxyl-containing monomers. The meaning and degree of preference for "substantially not containing" are also as important.
[0146] [1-4. Hydroxyl-containing monomers]
[0147] Hydroxyl-containing monomers refer to monomers that have at least one hydroxyl group within their molecule. Additionally, monomers that have at least one hydroxyl group and at least one carboxyl group within their molecule are carboxyl-containing monomers, not hydroxyl-containing monomers. There are no particular limitations on the aforementioned hydroxyl-containing monomers; specifically, examples include hydroxyethyl (meth)acrylate, hydroxypropyl (meth)acrylate, hydroxybutyl (meth)acrylate, hydroxypropyl (meth)acrylate, hydroxybutyl (meth)acrylate, hydroxybutyl (meth)acrylate, 6-hydroxyhexyl (meth)acrylate, hydroxyoctyl (meth)acrylate, hydroxydecyl (meth)acrylate, hydroxylauryl (meth)acrylate, and (4-hydroxymethylcyclohexyl) methacrylate, as well as vinyl alcohols and allyl alcohols. Among these, hydroxyl-containing monomers are preferred from the viewpoint of easily obtaining good cohesive strength and reliable adhesion at high temperatures; more preferably, 2-hydroxyethyl acrylate (HEA), 2-hydroxypropyl acrylate (HPA), and 4-hydroxybutyl acrylate (4HBA) are preferred. It should be noted that two or more hydroxyl-containing monomers can be used alone or in combination.
[0148] [1-5. Nitrogen-containing monomers]
[0149] A nitrogen-containing monomer is a monomer that has at least one nitrogen atom within a molecule. However, the aforementioned hydroxyl-containing monomers do not include the aforementioned nitrogen-containing monomers. That is, in this specification, monomers having both a hydroxyl group and a nitrogen atom within a molecule are included in nitrogen-containing monomers. In addition, monomers having at least one nitrogen atom and at least one carboxyl group within a molecule are carboxyl-containing monomers, not nitrogen-containing monomers.
[0150] From the viewpoint of improving foaming and peel resistance, N-vinyl cyclic amides and (meth)acrylamides are preferred as the aforementioned nitrogen-containing monomers. It should be noted that two or more nitrogen-containing monomers can be used alone or in combination.
[0151] From the viewpoint that it is easy to obtain good cohesive strength and easy to obtain adhesive reliability at high temperature, the N-vinyl cyclic amide shown in the following formula (1) is preferred as the above-mentioned N-vinyl cyclic amide.
[0152]
[0153] (In equation (1), R) 1 (representing a divalent organic group)
[0154] R in the above formula (1) 1 It is a divalent organic group, preferably a divalent saturated hydrocarbon group or an unsaturated hydrocarbon group, more preferably a divalent saturated hydrocarbon group (e.g., an alkylene group having 3 to 5 carbon atoms).
[0155] As the N-vinyl cyclic amide represented by the above formula (1), from the viewpoint of further improving foaming resistance and compatibility with benzotriazole compounds, N-vinyl-2-pyrrolidone (NVP), N-vinyl-2-piperidinone, N-vinyl-2-caprolactam, N,N-dimethyl (meth)acrylamide, N,N-diethyl (meth)acrylamide, N-vinyl-3-morpholinone, N-vinyl-1,3-oxazin-2-one, N-vinyl-3,5-morpholinedione, etc., are preferred, N-vinyl-2-pyrrolidone, N-vinyl-2-caprolactam, N,N-dimethyl (meth)acrylamide, N,N-diethyl (meth)acrylamide, etc., and N-vinyl-2-pyrrolidone is even more preferred.
[0156] Examples of the aforementioned (meth)acrylamides include (meth)acrylamide, N-alkyl (meth)acrylamide, and N,N-dialkyl (meth)acrylamide. Examples of the aforementioned N-alkyl (meth)acrylamides include N-ethyl (meth)acrylamide, N-isopropyl (meth)acrylamide, N-n-butyl (meth)acrylamide, and N-octylacrylamide. Furthermore, the aforementioned N-alkyl (meth)acrylamides also include (meth)acrylamides containing an amino group, such as dimethylaminoethyl (meth)acrylamide, diethylaminoethyl (meth)acrylamide, and dimethylaminopropyl (meth)acrylamide. Examples of the aforementioned N,N-dialkyl(meth)acrylamides include, for example, N,N-dimethyl(meth)acrylamide, N,N-diethyl(meth)acrylamide, N,N-dipropyl(meth)acrylamide, N,N-diisopropyl(meth)acrylamide, N,N-di(n-butyl)(meth)acrylamide, and N,N-di(tert-butyl)(meth)acrylamide.
[0157] Furthermore, the aforementioned (meth)acrylamide class also includes, for example, various N-hydroxyalkyl (meth)acrylamides. Examples of the aforementioned N-hydroxyalkyl (meth)acrylamides include, for example, N-hydroxymethyl (meth)acrylamide, N-(2-hydroxyethyl) (meth)acrylamide, N-(2-hydroxypropyl) (meth)acrylamide, N-(1-hydroxypropyl) (meth)acrylamide, N-(3-hydroxypropyl) (meth)acrylamide, N-(2-hydroxybutyl) (meth)acrylamide, N-(3-hydroxybutyl) (meth)acrylamide, N-(4-hydroxybutyl) (meth)acrylamide, and N-methyl-N-2-hydroxyethyl (meth)acrylamide.
[0158] Furthermore, the aforementioned (meth)acrylamide class also includes, for example, various N-alkoxyalkyl (meth)acrylamides. Examples of the aforementioned N-alkoxyalkyl (meth)acrylamides include, for example, N-methoxymethyl (meth)acrylamide and N-butoxymethyl (meth)acrylamide.
[0159] In addition, examples of nitrogen-containing monomers other than the aforementioned N-vinylcyclic amides and (meth)acrylamides include, for example, amino-containing monomers such as aminoethyl (meth)acrylate, dimethylaminoethyl (meth)acrylate, dimethylaminopropyl (meth)acrylate, and tert-butylaminoethyl (meth)acrylate; cyano-containing monomers such as acrylonitrile and methacrylonitrile; and monomers such as (meth)acryloylmorpholine, N-vinylpiperazine, N-vinylpyrrole, N-vinylimidazolium, N-vinylpyrazine, N-vinylmorpholine, N-vinylpyrazole, vinylpyridine, vinylpyrimidine, vinyloxazole, vinylisooxazole, vinylthiazole, vinylisothiazole, vinylpyridazine, (meth)acryloylpyrrolidone, (meth)acryloylpyrrolidine, (meth)acryloylpiperidine, and N-methylethyl... Monomers containing heterocyclic groups, such as alkenylpyrrolidone; maleimide monomers such as N-cyclohexylmaleimide, N-isopropylmaleimide, N-laurylmaleimide, and N-phenylmaleimide; itaconimide monomers such as N-methylitconimide, N-ethylitconimide, N-butylitconimide, N-octylitconimide, N-2-ethylhexylitconimide, N-laurylitconimide, and N-cyclohexylitconimide; succinimide monomers such as N-(meth)acryloyloxymethylenesuccinimide, N-(meth)acryloyl-6-oxyhexamethylenesuccinimide, and N-(meth)acryloyl-8-oxyoctamethylenesuccinimide; and isocyanate monomers such as 2-(meth)acryloyloxyethyl isocyanate.
[0160] When the aforementioned acrylic polymer (A) contains the aforementioned nitrogen-containing monomer as a monomer component constituting the polymer, the proportion of the aforementioned nitrogen-containing monomer in all monomer components (100 parts by weight) constituting the aforementioned acrylic polymer (A) is not particularly limited, but preferably 1 part by weight or more, more preferably 3 parts by weight or more, and even more preferably 5 parts by weight or more. When the above proportion is 1 part by weight or more, it is preferred from the viewpoint of easily obtaining good cohesive strength and easy obtaining adhesive reliability at high temperatures. Furthermore, the suppression of turbidity and durability under high humidity environments are further improved, and higher adhesive reliability for metal mesh wiring and silver nanowire layers can be obtained, which is also preferred. In addition, regarding the upper limit of the aforementioned nitrogen-containing monomer proportion, from the viewpoint of obtaining an adhesive layer with moderate flexibility and an adhesive layer with excellent transparency, it is preferably 30 parts by weight or less, more preferably 25 parts by weight or less, and even more preferably 20 parts by weight or less.
[0161] [1-6. Monomers containing alicyclic structures]
[0162] Alicyclic monomers refer to monomers that have polymerizable functional groups such as (meth)acryloyl or vinyl groups with unsaturated double bonds and possess an alicyclic structure. For example, alkyl (meth)acrylates with cycloalkyl groups are included among the above-mentioned alicyclic monomers. However, monomers having at least one alicyclic structure and at least one carboxyl group within their molecule are carboxyl-containing monomers, not alicyclic monomers. It should be noted that alicyclic monomers can be used alone or in combination of two or more.
[0163] The alicyclic structure in the above-mentioned monomers containing alicyclic structures is a cyclic hydrocarbon structure, preferably with 5 or more carbon atoms, more preferably with 6 to 24 carbon atoms, even more preferably with 6 to 15 carbon atoms, and particularly preferably with 6 to 10 carbon atoms.
[0164] Examples of the aforementioned alicyclic monomers include cyclopropyl methacrylate, cyclobutyl methacrylate, cyclopentyl methacrylate, cyclohexyl methacrylate, 3,3,5-trimethylcyclohexyl methacrylate, cyclopentyl methacrylate, cyclooctyl methacrylate, isobornyl methacrylate, dicyclopentyl methacrylate, HPMPA as shown in formula (2), TMA-2 as shown in formula (3), and HCPA as shown in formula (4). It should be noted that in formula (4), the bonding site between the cyclohexyl ring connected by the line and the structural formula within parentheses is not particularly limited. Among these, isobornyl methacrylate, cyclohexyl methacrylate, and 3,3,5-trimethylcyclohexyl methacrylate are preferred.
[0165]
[0166]
[0167] When the aforementioned acrylic polymer (A) contains the aforementioned alicyclic monomer as a monomeric component of the polymer, the proportion of the alicyclic monomer in all monomeric components (100 parts by weight) constituting the acrylic polymer (A) is not particularly limited. However, from the perspective of improving durability and obtaining higher adhesion reliability for metal mesh wiring and silver nanowire layers, it is preferable to have 3 parts by weight or more, more preferably 10 parts by weight or more. Furthermore, regarding the upper limit of the proportion of the alicyclic monomer, from the perspective of obtaining an adhesive layer with moderate flexibility, it is preferable to have 50 parts by weight or less, more preferably 40 parts by weight or less, and even more preferably 30 parts by weight or less.
[0168] [1-7. Other comonomers]
[0169] In addition to the nitrogen-containing monomers, hydroxyl-containing monomers, and alicyclic monomers mentioned above, other examples of comonomers in acrylic polymers (A) include, for instance, alkoxyalkyl esters of (meth)acrylate [e.g., 2-methoxyethyl ester, 2-ethoxyethyl ester, methoxytriethylene glycol ester, 3-methoxypropyl ester, 3-ethoxypropyl ester, 4-methoxybutyl ester, 4-ethoxybutyl ester, etc.]; and epoxy-containing monomers [e.g., glycidyl methacrylate]. [e.g., methyl glycidyl methacrylate]; sulfonic acid monomers [e.g., sodium vinyl sulfonate]; phosphate monomers; (meth)acrylates having aromatic hydrocarbon groups [e.g., phenyl (meth)acrylate, phenoxyethyl (meth)acrylate, benzyl (meth)acrylate]; vinyl esters [e.g., vinyl acetate, vinyl propionate]; aromatic vinyl compounds [e.g., styrene, vinyltoluene]; olefins or dienes [e.g., ethylene, propylene, butadiene, isoprene, isobutylene]; vinyl ethers [e.g., vinyl alkyl ethers]; vinyl chloride, etc.
[0170] [1-8. Hydrogenated polyolefin resins (B)]
[0171] The adhesive layer of this invention is an acrylic adhesive layer in which an acrylic polymer (A) is used as the main component and a hydrogenated polyolefin resin (B) that exhibits liquid flowability at 25°C is blended. The hydrogenated polyolefin resin (B) exhibiting liquid flowability at 25°C means that its viscosity, measured at 25°C using a type B viscometer, is 10,000 mPa·s or less. The hydrogenated polyolefin resin (B) can be used alone or in combination of two or more types.
[0172] Hydrogenated polyolefin resin (B) is a material with a low dielectric constant. Since it exhibits liquid flowability at 25°C (room temperature), by incorporating it into the acrylic polymer (A) of this invention, the stress relief of the adhesive layer of this invention can be improved without increasing the dielectric constant or requiring a reduction in the molecular weight of the acrylic polymer (A). This allows for the maintenance of adhesive strength and bonding reliability at high temperatures, and improved height difference tracking. Furthermore, the hydrogenated polyolefin resin (B) has excellent compatibility with the acrylic polymer (A), making it preferable in terms of maintaining a higher degree of transparency in the adhesive layer of this invention.
[0173] Hydrogenated polyolefin resin (B) is obtained by reducing the carbon-carbon double bonds contained in the polyolefin resin through a hydrogenation reaction. Because hydrogenated polyolefin resin (B) has fewer carbon-carbon double bonds within its molecule, it is less prone to polymerization inhibition, reduction in polymerization rate, and molecular weight degradation when the adhesive layer of the present invention is cured, for example, by ultraviolet irradiation. Therefore, it can maintain a high degree of adhesive reliability at high temperatures.
[0174] Regarding the hydrogenation rate of the hydrogenated polyolefin resin (B), from the viewpoint of minimizing polymerization inhibition and ensuring adhesive reliability at high temperatures, a hydrogenation rate of 90% or higher is preferred, more preferably 95% or higher, and even more preferably 97% or higher. There is no particular upper limit to the hydrogenation rate; theoretically it is 100%, but practically it can be 99.9% or lower, or 99.8% or lower. It should be noted that the hydrogenation rate of the hydrogenated polyolefin resin (B) can be determined by utilizing… 1 The amount of residual double bonds in hydrogenated polyolefin resin (B) can be determined by ¹H-NMR determination.
[0175] For the iodine value (Ig / 100g) of hydrogenated polyolefin resin (B), from the viewpoint of minimizing polymerization inhibition and ensuring reliable adhesion at high temperatures, a value of 30 or less is preferred, more preferably 25 or less, and even more preferably 20 or less. The lower limit of the iodine value is not particularly limited and can be 0.1 or more, or 0.2 or more. It should be noted that the iodine value is determined according to JIS K 0070-1992.
[0176] For the hydrogenated polyolefin resin (B), the number average molecular weight (Mn) is preferably 1000 to 5000, which is beneficial for imparting appropriate stress relief and flowability to the adhesive layer and improving compatibility with the acrylic polymer (A). For this number average molecular weight (Mn), which is beneficial for imparting appropriate stress relief and flowability to the adhesive layer, it is preferably 1000 or more, more preferably 1500 or more, and even more preferably 1800 or more. For the purpose of improving compatibility with the acrylic polymer (A) and maintaining the transparency of the adhesive layer of the present invention, the number average molecular weight (Mn) is preferably 5000 or less, more preferably 4800 or less, and even more preferably 4600 or less.
[0177] For the polydispersity (Mw / Mn) of the hydrogenated polyolefin resin (B), a value of 2.0 or less, and more preferably 1.8 or less, is preferred in terms of imparting appropriate stress relief and flowability to the adhesive layer, improving compatibility with the acrylic polymer (A), maintaining high transparency, and suppressing haze. The lower limit of the polydispersity is not particularly limited, and practically it can be 1.0 or more, or 1.1 or more.
[0178] The number-average molecular weight (Mn) and polydispersity (Mw / Mn) of the hydrogenated polyolefin resin (B) were determined by gel permeation chromatography (GPC) and calculated based on polystyrene.
[0179] As a hydrogenated polyolefin resin (B), it includes hydrogenated polyolefins, hydrogenated polyolefin polyols, etc. Hydrogenated polyolefins and hydrogenated polyolefin polyols can be used individually or in combination.
[0180] The aforementioned hydrogenated polyolefins are hydrides of polymers (polyolefins) having structural units derived from olefins. Hydrogenated polyolefins include hydrides of homopolymers and copolymers of α-olefins such as ethylene, propylene, 1-butene, isobutene, and 1-hexene; diene compounds such as butadiene and isoprene; and aromatic vinyl compounds such as styrene. Hydrogenated polyolefins are preferably hydrides of homopolymers or copolymers of diene compounds; examples include hydrogenated polybutadiene and hydrogenated polyisoprene.
[0181] The aforementioned hydrogenated polyolefin polyol is a compound obtained by modifying the terminal hydroxyl groups of the aforementioned hydrogenated polyolefin. Preferably, the hydrogenated polyolefin polyol is a hydroxyl-modified homopolymer or copolymer of a diene compound; examples include hydrogenated polybutadiene polyol and hydrogenated polyisoprene polyol.
[0182] As the hydrogenated polyolefin resin (B), hydrogenated polybutadiene and / or hydrogenated polybutadiene polyol are preferred in terms of imparting appropriate stress relief and flowability to the adhesive layer and improving compatibility with the acrylic polymer (A). Hydrogenated polybutadiene and hydrogenated polybutadiene polyol can be used individually or in combination.
[0183] As hydrogenated polybutadiene, the substance shown in formula (5) below is preferred, and as hydrogenated polybutadiene polyol, the substance shown in formula (6) below is preferred.
[0184]
[0185] In the above formula, m represents the degree of polymerization of hydrogenated polybutadiene.
[0186] Commercially available products can be used as hydrogenated polyolefin resins (B). Examples of commercially available hydrogenated polyolefin resins (B) include those with trade names such as "GI-1000", "GI-2000", "GI-3000", "BI-2000", and "BI-3000" (all manufactured by Nippon Soda Co., Ltd.), and "EPOL" (manufactured by Idemitsu Kosan Co., Ltd.).
[0187] The content of hydrogenated polyolefin resin (B) in the adhesive layer is not particularly limited. For example, it is preferably 3 to 35 parts by weight, more preferably 5 to 33 parts by weight, and even more preferably 8 to 30 parts by weight relative to 100 parts by weight of acrylic polymer (A). A content of 3 parts by weight or more of hydrogenated polyolefin resin (B) is preferred in terms of imparting excellent height difference absorption to the adhesive layer. On the other hand, a content of 35 parts by weight or less of hydrogenated polyolefin resin (B) is preferred in terms of improving the gelation rate of the adhesive layer of the present invention, preventing cutability (end contamination) during cutting processing, maintaining high adhesion at high temperatures, and improving adhesion reliability. Furthermore, it is also preferred in terms of improving processability by preventing process contamination caused by contamination at the cut ends of the adhesive layer.
[0188] [1-9. Polyfunctional (meth)acrylates]
[0189] The adhesive layer of the present invention preferably further comprises a polyfunctional (meth)acrylate. The polyfunctional (meth)acrylate acts as a crosslinking component, giving the adhesive layer moderate cohesive strength and easily improving adhesion and height difference absorption.
[0190] Examples of multifunctional (meth)acrylates include, for example, hexanediol dimethacrylate, butanediol dimethacrylate, polyethylene glycol dimethacrylate, polypropylene glycol dimethacrylate, neopentyl glycol dimethacrylate, pentaerythritol dimethacrylate, pentaerythritol trimethacrylate, dipentaerythritol hexamethacrylate, trimethylolpropane trimethacrylate, tetramethylolmethane trimethacrylate, allyl methacrylate, ethylene methacrylate, divinylbenzene, epoxy acrylates, polyester acrylates, and urethane acrylates. It should be noted that multifunctional (meth)acrylates can be used alone or in combination of two or more types.
[0191] The content (ratio) of polyfunctional (meth)acrylate is not particularly limited, but relative to 100 parts by weight of acrylic polymer (A), it is preferably 0.001 to 0.5 parts by weight, more preferably 0.001 to 0.35 parts by weight, and even more preferably 0.002 to 0.2 parts by weight. When the content of polyfunctional (meth)acrylate is 0.001 parts by weight or more, the adhesive layer has moderate cohesive strength, and the adhesion and height difference absorption are easily improved, which is preferred. When the content of polyfunctional (meth)acrylate is 0.5 parts by weight or less, it is less likely to cause changes in physical properties and corrosion over time due to unreacted crosslinking points, which is also preferred.
[0192] [1-10. Rust Inhibitor]
[0193] The adhesive layer of the present invention preferably also contains a rust inhibitor. The inclusion of a rust inhibitor in the adhesive layer is preferred in that it provides excellent corrosion protection for metal wiring such as metal mesh wiring and silver nanowire layers.
[0194] Rust inhibitors are compounds that prevent metals from rusting and corroding. There are no particular limitations on the types of rust inhibitors; examples include amine compounds, benzotriazole compounds, and nitrites. Other examples include ammonium benzoate, ammonium phthalate, ammonium stearate, ammonium palmitate, ammonium oleate, ammonium carbonate, dicyclohexylamine benzoate, urea, urotropine, thiourea, phenyl carbamate, and cyclohexylammonium-N-cyclohexylcarbamate (CHC). It should be noted that rust inhibitors can be used alone or in combination of two or more.
[0195] Examples of the aforementioned amine compounds include, for example, hydroxyl-containing amine compounds such as 2-amino-2-methyl-1-propanol, monoethanolamine, monoisopropanolamine, diethylethanolamine, ammonia, and ammonia water; cyclic amines such as morpholine; cyclic alkylamine compounds such as cyclohexylamine; and linear alkylamines such as 3-methoxypropylamine. Additionally, examples of nitrites include, for example, dicyclohexylammonium nitrite (DICHAN), diisopropylammonium nitrite (DIPAN), sodium nitrite, potassium nitrite, and calcium nitrite.
[0196] The content of the aforementioned rust inhibitor is not particularly limited, but it is preferably 0.02 to 15 parts by weight relative to 100 parts by weight of the acrylic polymer (A). A content of 0.02 parts by weight or more readily yields good anti-corrosion performance and is therefore preferred. On the other hand, a content of less than 15 parts by weight readily ensures transparency and, moreover, readily ensures adhesive reliability such as resistance to foaming and peeling.
[0197] Of the aforementioned rust inhibitors, benzotriazole compounds are preferred in terms of compatibility with the acrylic polymer (A), transparency, and, more importantly, the fact that the addition of the rust inhibitor does not easily hinder the reaction (crosslinking, polymerization) of the acrylic polymer (A). In particular, benzotriazole compounds are preferred in terms of achieving a good balance between high-level adhesive reliability, transparency, and corrosion resistance, as well as excellent appearance.
[0198] The content of the benzotriazole compound is not particularly limited, but is preferably 0.02 to 3 parts by weight, more preferably 0.02 to 2.5 parts by weight, and even more preferably 0.02 to 2 parts by weight, relative to 100 parts by weight of the acrylic polymer (A). Because the amount of the benzotriazole compound is below a certain level, adhesive reliability, such as foaming peel resistance, can be reliably ensured, and consequently, the increase in haze of the adhesive sheet can be reliably prevented.
[0199] As for the above-mentioned benzotriazole compounds, there are no particular limitations as long as they have a benzotriazole skeleton, and it is preferred from the viewpoint of obtaining a better anti-corrosion effect from the structure shown in the following formula (7).
[0200]
[0201] (wherein, in equation (7) above, R) 2 and R 3 Same or different, R 2 Substituents on the benzene ring represent alkyl (1-6 carbons), alkoxy (1-6 carbons), aryl (6-14 carbons), amino, mono- or di-carbon groups. 1-10 Alkylamino, amino-C 1-6 Alkyl, mono- or di-C 1-10 Alkylamino-C 1-6 Alkyl, mercapto, alkoxycarbonyl with 1 to 6 carbon atoms, or alkoxy group with 1 to 6 carbon atoms, etc., where n is an integer from 0 to 4, and when n is 2 or more, n R 2 They can be the same or different, R 3 Represents hydrogen atom, alkyl group having 1 to 12 carbon atoms, alkoxy group having 1 to 12 carbon atoms, aryl group having 6 to 14 carbon atoms, amino group, mono- or di-carbon atom. 1-10 Alkylamino, amino-C 1-6 Alkyl, mono- or di-C 1-10 Alkylamino-C 1-6 Substituents include alkyl, mercapto, alkoxy carbonyl (1-12 carbon atoms), or alkoxy group (1-12 carbon atoms).
[0202] From the perspective of achieving superior corrosion resistance, as R 2 Preferably, it is an alkyl group or alkoxycarbonyl group having 1 to 3 carbon atoms, and more preferably a methyl group. In addition, n is preferably 0 or 1.
[0203] Starting from the same point of view, as R 3 Preferred hydrogen atoms, single or two C atoms 1-10 Alkylamino-C 1-6 Alkyl groups, and more preferably hydrogen atoms and two-C atoms. 1~8 Alkylamino C 1~4 Alkyl groups, etc.
[0204] [1-11. Silane coupling agents]
[0205] The adhesive layer of the present invention preferably further contains a silane coupling agent. The presence of a silane coupling agent in the adhesive layer is preferred in that it readily yields excellent adhesion to glass (especially excellent adhesion reliability to glass under high temperature and humidity).
[0206] There are no particular limitations on the silane coupling agents mentioned above, and examples include γ-epoxypropoxypropyltrimethoxysilane, γ-epoxypropoxypropyltriethoxysilane, γ-aminopropyltrimethoxysilane, and N-phenyl-aminopropyltrimethoxysilane. Among these, γ-epoxypropoxypropyltrimethoxysilane is preferred. Furthermore, commercially available products such as "KBM-403" (manufactured by Shin-Etsu Chemical Co., Ltd.) can also be cited as examples of the aforementioned silane coupling agents. It should be noted that two or more silane coupling agents can be used alone or in combination.
[0207] The content of the silane coupling agent is not particularly limited. From the perspective of improving the bonding reliability of glass, it is preferred to be 0.01 to 1 part by weight, more preferably 0.03 to 0.5 parts by weight, relative to 100 parts by weight of acrylic polymer (A).
[0208] [1-12. Antioxidants]
[0209] The adhesive layer of the present invention preferably further contains an antioxidant. The inclusion of an antioxidant in the adhesive layer is preferable in preventing oxidative degradation of the adhesive sheet during storage.
[0210] Antioxidants can prevent the hindrance caused by oxygen in free radicals generated by free radical generators, thereby ensuring a stable gel ratio (degree of crosslinking). In addition, they can suppress the increase in peel force of the release film (isolated body) applied to the adhesive layer and can increase the gel ratio.
[0211] As the aforementioned antioxidants, examples include phenolic, phosphorus-based, sulfur-based, and amine-based antioxidants, and at least one selected from these is used. Among these, phenolic antioxidants are preferred. It should be noted that antioxidants can be used alone or in combination of two or more.
[0212] Specific examples of phenolic antioxidants, and examples of monocyclic phenolic compounds, include 2,6-di-tert-butyl-p-cresol, 2,6-di-tert-butyl-4-ethylphenol, 2,6-dicyclohexyl-4-methylphenol, 2,6-diisopropyl-4-ethylphenol, 2,6-di-tert-pentyl-4-methylphenol, 2,6-di-tert-octyl-4-n-propylphenol, 2,6-dicyclohexyl-4-n-octylphenol, 2-isopropyl-4-methyl-6-tert-butylphenol, 2-tert-butyl-4-ethyl-6-tert-octylphenol, 2-isobutyl-4-ethyl-6-tert-hexylphenol, 2-cyclohexyl-4-n-butyl-6-isopropylphenol, and styrene-modified mixed cresols. DL-α-tocopherol, stearyl β-(3,5-di-tert-butyl-4-hydroxyphenyl)propionate, etc., as dicyclic phenolic compounds, include 2,2'-methylenebis(4-methyl-6-tert-butylphenol), 4,4'-butylidenebis(3-methyl-6-tert-butylphenol), 4,4'-thiobis(3-methyl-6-tert-butylphenol), 2,2'-thiobis(4-methyl-6-tert-butylphenol), 4,4'-methylenebis(2,6-di-tert-butylphenol), 2,2'-methylenebis[6-(1-methylcyclohexyl)-p-cresol], 2,2'-ethylidenebis(4,6-di-tert-butylphenol), 2,2'-butylidenebis Examples of tricyclic phenolic compounds include 2-tert-butyl-4-methylphenol, 3,6-dioxaoctanemethylbis[3-(3-tert-butyl-4-hydroxy-5-methylphenyl)propionate], triethylene glycol bis[3-(3-tert-butyl-5-methyl-4-hydroxyphenyl)propionate], 1,6-hexanediol bis[3-(3,5-di-tert-butyl-4-hydroxyphenyl)propionate], and 2,2'-thiodiethylenebis[3-(3,5-di-tert-butyl-4-hydroxyphenyl)propionate]. Examples of tetracyclic phenolic compounds include tert-butylbenzyl isocyanurate, 1,3,5-tris[(3,5-di-tert-butyl-4-hydroxyphenyl)propionyloxyethyl]isocyanurate, tris(4-tert-butyl-2,6-dimethyl-3-hydroxybenzyl)isocyanurate, and 1,3,5-trimethyl-2,4,6-tris(3,5-di-tert-butyl-4-hydroxybenzyl)benzene. Examples of tetracyclic phenolic compounds include tetra[methylene-3-(3,5-di-tert-butyl-4-hydroxyphenyl)propionate]methane. Examples of phosphorus-containing phenolic compounds include bis(3,5-di-tert-butyl-4-hydroxybenzylphosphonate ethyl ester)calcium and bis(3,5-di-tert-butyl-4-hydroxybenzylphosphonate ethyl ester)nickel.
[0213] Specific examples of phosphorus-based antioxidants include trioctyl phosphite, trilauryl phosphite, tri(tridecyl) phosphite, triisodecyl phosphite, phenyl diisooctyl phosphite, phenyl diisodecyl phosphite, phenyl di(tridecyl) phosphite, diphenyl isooctyl phosphite, diphenyl isodecyl phosphite, diphenyl tridecyl phosphite, triphenyl phosphite, tri(nonylphenyl) phosphite, tri(2,4-di-tert-butylphenyl) phosphite, and tri(butoxyethyl) phosphite. Tetra(tetranyl)-4,4'-butylenebis(3-methyl-6-tert-butylphenol)-diphosphite, 4,4'-isopropylene-diphenol alkyl phosphite (however, the alkyl group has approximately 12 to 15 carbon atoms), 4,4'-isopropylenebis(2-tert-butylphenol)·di(nonylphenyl) phosphite, tri(biphenyl) phosphite, tetra(tetranyl)-1,1,3-tris(2-methyl-5-tert-butyl-4-hydroxyphenyl)butane diphosphite, tris(3,5-ditert-butyl-4-hydroxyphenyl)butane diphosphite, tris(3,5-ditert-butyl-4-hydroxyphenyl)butane diphosphite, -Hydroxyphenyl) phosphite, hydrogenated 4,4'-isopropylidene diphenol polyphosphite, bis(octylphenyl)·bis[4,4'-butylidene bis(3-methyl-6-tert-butylphenol)]·1,6-hexanediol diphosphite, hexa(tetranyl)-1,1,3-tris(2-methyl-4-hydroxy-5-tert-butylphenol) diphosphite, tris[4,4'-isopropylidene bis(2-tert-butylphenol)] phosphite, tris(1,3-distearyloxyisopropyl) phosphite, 9,1 O-Dihydro-9-phosphaphenanthrene-10-oxide, tetrakis(2,4-di-tert-butylphenyl)-4,4'-biphenyl diphosphonate, distearate pentaerythritol diphosphite, di(nonylphenyl) pentaerythritol diphosphite, phenyl-4,4'-isopropylidene diphenol pentaerythritol diphosphite, bis(2,4-di-tert-butylphenyl) pentaerythritol diphosphite, bis(2,6-di-tert-butyl-4-methylphenyl) pentaerythritol diphosphite, and phenylbisphenol-A-pentaerythritol diphosphite, etc.
[0214] As sulfur-based antioxidants, dialkyl thiodipropionates and polyol esters of alkyl thiopropionic acids are preferred. Among the dialkyl thiodipropionates used here, dialkyl thiodipropionates having alkyl groups of 6 to 20 carbon atoms are preferred; furthermore, among the polyol esters of alkyl thiopropionic acids, polyol esters of alkyl thiopropionic acids having alkyl groups of 4 to 20 carbon atoms are preferred. Examples of polyols constituting the polyol ester include glycerol, trimethylolethane, trimethylolpropane, pentaerythritol, and trihydroxyethyl isocyanurate. Examples of such dialkyl thiodipropionates include, for example, dilauryl thiodipropionate, dimyristyl thiodipropionate, and distearatel thiodipropionate. On the other hand, examples of polyol esters of alkyl thiopropionic acid include, for example, glyceryl tributyl thiopropionate, glyceryl trioctyl thiopropionate, glyceryl trilauryl thiopropionate, glyceryl tristearyl thiopropionate, trimethylolethane tributyl thiopropionate, trimethylolethane trioctyl thiopropionate, trimethylolethane trilauryl thiopropionate, trimethylolethane tristearyl thiopropionate, pentaerythritol tetrabutyl thiopropionate, pentaerythritol tetraoctyl thiopropionate, pentaerythritol tetralauryl thiopropionate, and pentaerythritol tetrastearyl thiopropionate.
[0215] Specific examples of amine antioxidants include bis(2,2,6,6-tetramethyl-4-piperidinyl) sebacate, dimethyl succinate and 1-(2-hydroxyethyl)-4-hydroxy-2,2,6,6-tetramethylpiperidinylethanol condensate, N,N',N”,N”'-tetra-(4,6-bis-(butyl-(N-methyl-2,2,6,6-tetramethylpiperidin-4-yl)amino)-triazin-2-yl)-4,7-diazadecane-1,10-diamine, dibutylamine·1,3,5-triazine·N,N'-bis(2,2,6,6-tetramethyl-4-piperidinyl-1,6-hexamethylenediamine and N-(2,2,6,6-tetramethyl-4-piperidinyl)butylamine condensate, and poly[{6- (1,1,3,3-Tetramethylbutyl)amino-1,3,5-triazine-2,4-diyl}{(2,2,6,6-tetramethyl-4-piperidinyl)imino}hexamethylene{(2,2,6,6-tetramethyl-4-piperidinyl)imino}, tetra(2,2,6,6-tetramethyl-4-piperidinyl)-1,2,3,4-butanetetracarboxylate, 2,2,6,6-tetramethyl-4-piperidinylbenzoate, bis-(1,2,6,6-pentamethyl-4-piperidinyl)-2-(3,5-di-tert-butyl-4-hydroxybenzyl)-2-n-butylmalonate, bis-(N-methyl-2,2,6,6-tetramethyl-4-piperidinyl)sebacate, 1,1'-(1,2-ethanediyl)bis(3,3 [2,2,6,6-Tetramethylpiperazinone], [mixed 2,2,6,6-tetramethyl-4-piperidinyl / tridecyl)-1,2,3,4-butanetetracarboxylate], [mixed 1,2,2,6,6-pentamethyl-4-piperidinyl / tridecyl)-1,2,3,4-butanetetracarboxylate], [mixed 2,2,6,6-tetramethyl-4-piperidinyl / β,β,β',β'-tetramethyl-3,9-[2,4,8,10-tetraoxellaspiro(5,5)undecane]diethyl]-1,2,3,4-butanetetracarboxylate], [mixed 1,2,2,6,6-pentamethyl-4-piperidinyl / β,β,β',β'-tetramethyl-3,9-[2,4,8,10-tetraoxellaspiro(5,5)undecane]diethyl] -1,2,3,4-Butanetetracarboxylate, N,N'-bis(3-aminopropyl)ethylenediamine-2,4-bis[N-butyl-N-(1,2,2,6,6-pentamethyl-4-piperidinyl)amino]-6-chloro-1,3,5-triazine condensate, poly[6-N-morpholino-1,3,5-triazine-2,4-diyl][(2,2,6,6-tetramethyl-4-piperidinyl)imino]hexamethylene[(2,2,6,6-tetramethyl-4-piperidinyl)imide], N,N'-bis(2,2,6,6-tetramethyl-4-piperidinyl)hexamethylenediamine and 1,2-dibromoethane condensate, [N-(2,2,6,6-tetramethyl-4-piperidinyl)-2-methyl-2-(2,2,6,6,[6-Tetramethyl-4-piperidinyl]imino]propionamide, etc.
[0216] The content of the antioxidant is not particularly limited, but from the viewpoint of preventing oxidation of the polymer based on free radical generators, it is preferably set to 0.05 parts by weight or more relative to 100 parts by weight of the acrylic polymer (A). On the other hand, if the content of the aforementioned antioxidant increases, the proportion of free radicals generated by the free radical generator that are captured increases. As a result, it is easy to cause crosslinking resistance in the adhesive layer formed by the aforementioned adhesive composition, thereby reducing the gelation rate of the adhesive layer and resulting in poor appearance. From this viewpoint, the content of the antioxidant is preferably set to 5 parts by weight or less, and further to 1.5 parts by weight or less, relative to 100 parts by weight of the acrylic polymer (A). From the viewpoint of balancing the above-mentioned assurance of gelation rate and the antioxidant properties of the polymer, the content of the aforementioned antioxidant is preferably 0.05 to 5 parts by weight, further preferably 0.1 to 1.5 parts by weight, and further preferably 0.1 to 1.0 parts by weight, relative to 100 parts by weight of the acrylic polymer (A).
[0217] [1-13. Crosslinking agent]
[0218] The adhesive composition of the present invention, as described above, is preferably not solvent-based; that is, the adhesive layer of the present invention preferably does not contain or substantially does not contain a crosslinking agent.
[0219] Examples of crosslinking agents include, in addition to isocyanate-based, epoxy-based, melamine-based, and peroxide-based crosslinking agents, urea-based, metal alkoxide-based, metal chelate-based, metal salt-based, carbodiimide-based, oxazoline-based, aziridine-based, and amine-based crosslinking agents. In particular, the adhesive layer of the present invention preferably does not contain or substantially does not contain isocyanate-based and / or epoxy-based crosslinking agents, and more preferably does not contain or substantially does not contain isocyanate-based crosslinking agents.
[0220] Examples of isocyanate-based crosslinking agents (polyfunctional isocyanate compounds) include, for example, lower aliphatic polyisocyanates such as 1,2-ethylene diisocyanate, 1,4-butylene diisocyanate, and 1,6-hexamethylene diisocyanate; alicyclic polyisocyanates such as cyclopentylene diisocyanate, cyclohexylene diisocyanate, isophorone diisocyanate, hydrogenated toluene diisocyanate, and hydrogenated xylene diisocyanate; and aromatic polyisocyanates such as 2,4-toluene diisocyanate, 2,6-toluene diisocyanate, 4,4'-diphenylmethane diisocyanate, and phenyl dimethyl diisocyanate. In addition, as the aforementioned isocyanate-based crosslinking agents, examples include commercially available products such as trimethylolpropane / toluene diisocyanate adduct [manufactured by Nippon Polyurethane Industry Co., Ltd., trade name "CORONATE L"], trimethylolpropane / hexamethylene diisocyanate adduct [manufactured by Nippon Polyurethane Industry Co., Ltd., trade name "CORONATE HL"], and trimethylolpropane / phenylenedimethyl diisocyanate adduct [manufactured by Mitsui Chemicals Co., Ltd., trade name "TAKENATE D-110N"].
[0221] Examples of epoxy crosslinking agents (multifunctional epoxy compounds) include, for instance, N,N,N',N'-tetraglycidyl-m-phenylenediamine, diglycidyl aniline, 1,3-bis(N,N-diglycidylaminomethyl)cyclohexane, 1,6-hexanediol diglycidyl ether, neopentyl glycol diglycidyl ether, ethylene glycol diglycidyl ether, propylene glycol diglycidyl ether, polyethylene glycol diglycidyl ether, polypropylene glycol diglycidyl ether, and sorbitan. Sugar alcohol polyglycidyl ether, glycerol polyglycidyl ether, pentaerythritol polyglycidyl ether, polyglycerol polyglycidyl ether, sorbitan polyglycidyl ether, trimethylolpropane polyglycidyl ether, diglycidyl adipate, diglycidyl phthalate, triglycidyl-tris(2-hydroxyethyl) isocyanurate, resorcinol diglycidyl ether, bisphenol-S-d-diglycidyl ether, and epoxy resins having two or more epoxy groups within their molecules, etc. Additionally, as the aforementioned epoxy crosslinking agents, commercially available products such as those manufactured by Mitsubishi Gas Chemical Co., Ltd., under the trade name "TETRAD C," can also be cited.
[0222] In the adhesive layer of the present invention, "substantially free" crosslinking agent means that, except where crosslinking agent is unavoidably mixed in, no crosslinking agent is actively mixed in. Specifically, when the content of crosslinking agent in the adhesive layer is 1.0% by weight or less (preferably 0.5% by weight or less, more preferably 0.2% by weight or less) relative to the total amount of the adhesive layer (total weight, 100% by weight), it can be said to be substantially free. In addition, when the content of crosslinking agent in the adhesive layer is preferably 0.05 parts by weight or less (e.g., 0 to 0.05 parts by weight), more preferably 0.01 parts by weight or less (e.g., 0 to 0.01 parts by weight), and more preferably 0.001 parts by weight or less (e.g., 0 to 0.001 parts by weight) relative to the total amount of monomer components constituting the acrylic polymer (A) (100 parts by weight), it can also be said to be substantially free.
[0223] [1-14. Additives]
[0224] The adhesive layer of this invention may contain, as needed and without impairing the characteristics of the invention, known additives such as crosslinking accelerators, adhesive resins (rosin derivatives, polyterpenoid resins, oil-soluble phenols, etc.), antioxidants, fillers, colorants (pigments, dyes, etc.), ultraviolet absorbers, chain transfer agents, plasticizers, softeners, surfactants, and antistatic agents. It should be noted that such additives may be used alone or in combination of two or more.
[0225] [2. Adhesive sheet]
[0226] The adhesive sheet of the present invention is only required to have the adhesive layer of the present invention (an adhesive layer formed by the adhesive composition of the present invention), and is not particularly limited in other respects.
[0227] The adhesive sheet of the present invention can be a double-sided adhesive sheet with adhesive layer surfaces on both sides, or a single-sided adhesive sheet with adhesive layer surfaces on only one side. From the viewpoint of bonding two components together, a double-sided adhesive sheet is preferred. It should be noted that the term "adhesive sheet" in this specification also includes strip-shaped cases, i.e., "adhesive tape." Furthermore, the adhesive layer surface is sometimes referred to as the "adhesive surface" in this specification.
[0228] The adhesive sheet of the present invention may have an isolator (release liner) on the adhesive surface until it is used.
[0229] The adhesive sheet of the present invention can be a so-called "substrate-free" adhesive sheet (hereinafter, sometimes referred to as "substrate-free adhesive sheet") that does not have a substrate (substrate layer), or it can be an adhesive sheet with a substrate (hereinafter, sometimes referred to as "substrate-supported adhesive sheet"). Examples of the aforementioned substrate-free adhesive sheet include, for example, a double-sided adhesive sheet formed solely of the aforementioned adhesive layer, and a double-sided adhesive sheet formed of the aforementioned adhesive layer and an adhesive layer other than the aforementioned adhesive layer (sometimes referred to as "other adhesive layers"). On the other hand, examples of a substrate-supported adhesive sheet include an adhesive sheet having the aforementioned adhesive layer on at least one side of the substrate. Among these, a substrate-free adhesive sheet (substrate-free double-sided adhesive sheet) is preferred, and a substrate-free double-sided adhesive sheet formed solely of the aforementioned adhesive layer is more preferred. It should be noted that the aforementioned "substrate (substrate layer)" does not include the separator that is peeled off during the use (application) of the adhesive sheet.
[0230] The adhesive sheet of the present invention is preferably a substrate-free adhesive sheet. This is because: when using a substrate-based adhesive sheet, it can also prevent the degradation of sensor function and malfunction caused by ion migration due to the penetration of hygroscopic and corrosive gases from the side end to a certain extent. Therefore, a substrate-free adhesive sheet is more significant in that it can impart a low dielectric constant.
[0231] [2-1. Other physical properties of adhesive sheets]
[0232] The adhesive sheet of the present invention does not have a particularly limited 180° peel adhesion force on acrylic sheets at 25°C and a tensile speed of 300 mm / min (especially the 180° peel adhesion force on the acrylic sheet at 25°C and a tensile speed of 300 mm / min provided by the adhesive layer (the adhesive layer formed by the adhesive composition of the present invention)). From the viewpoint that a high adhesion force can result in sufficient adhesion to the metal surface and improved corrosion resistance, a force of 10 N / 20 mm or more is preferred, more preferably 12 N / 20 mm or more, and even more preferably 14 N / 20 mm or more is preferred. When the adhesive sheet of the present invention has a 180° peel adhesion force of 10 N / 20 mm on acrylic sheets at 25°C and a tensile speed of 300 mm / min, it is easy to obtain good adhesion to the acrylic sheets and good suppression of lifting in height differences, which is preferred. It should be noted that the adhesive sheet of the present invention does not particularly limit the upper limit of the 180° peel adhesion force of the acrylic sheet at 25°C and a tensile speed of 300 mm / min, for example, it is 40 N / 20 mm, more preferably 60 N / 20 mm. The 180° peel adhesion force of the acrylic sheet at 25°C and a tensile speed of 300 mm / min is determined by the following method for measuring the 180° peel adhesion force.
[0233] The 180° peel bond strength of the acrylic sheet at 25°C and a tensile speed of 300 mm / min was determined using the method described above for measuring 180° peel bond strength. There are no particular limitations on the acrylic sheet used; for example, PMMA sheets (trade name "ACRYLITE", manufactured by MITSUBISHI RAYON CO., LTD.) can be cited.
[0234] The adhesive strength and adhesive ratio of the adhesive sheet to the acrylic sheet of the present invention can be adjusted by adjusting the monomer composition of the acrylic polymer (A), the type of hydrogenated polyolefin resin (B), and the mixing ratio of the acrylic polymer (A) and the hydrogenated polyolefin resin (B).
[0235] [2-2. Manufacturing method of adhesive sheet]
[0236] The adhesive sheet of the present invention is not particularly limited, and it is preferably manufactured according to known or conventional manufacturing methods. For example, when the adhesive sheet of the present invention is a substrate-free adhesive sheet, it is obtained by forming the adhesive layer on the spacer using the method described above. In addition, when the adhesive sheet of the present invention is a substrate-based adhesive sheet, it can be obtained by directly forming the adhesive layer on the surface of the substrate (direct writing method), or by temporarily forming the adhesive layer on the spacer and then transferring (adhering) it to the substrate, thereby providing the adhesive layer on the substrate (transfer printing method).
[0237] [2-3. Adhesive layer of the adhesive sheet]
[0238] (Storage modulus at 25℃)
[0239] The storage modulus of the adhesive layer (the adhesive layer formed from the adhesive composition of the present invention) at 25°C is not particularly limited, but is preferably 0.01 MPa or more, more preferably 0.05 MPa or more, and even more preferably 0.1 MPa or more. When the storage modulus is 0.01 MPa or more, good adhesive reliability is easily obtained, which is preferred. Furthermore, from the viewpoint of height difference tracking, the storage modulus of the adhesive layer at 25°C is preferably 0.5 MPa or less, more preferably 0.4 MPa or less. The storage modulus of the adhesive layer is measured by dynamic viscoelasticity.
[0240] The energy storage modulus of the adhesive layer of the present invention can be adjusted by adjusting the monomer composition of the acrylic polymer (A), the type of hydrogenated polyolefin resin (B), and the mixing ratio of the acrylic polymer (A) and the hydrogenated polyolefin resin (B).
[0241] (300% tensile residual stress)
[0242] The 300% tensile residual stress of the adhesive layer in this invention is not particularly limited, but is preferably 7 to 16 N / cm. 2 More preferably 7–15 N / cm 2 A further preferred value is 7–14 N / cm. 2 The aforementioned 300% tensile residual stress is 7 N / cm. 2 At the above levels, good resistance to foaming and peeling is easily obtained, making it the preferred option. Furthermore, the residual stress at 300% tensile strength is 16 N / cm. 2 The following conditions result in good stress relief and easy achievement of good height difference tracking, making it the preferred option.
[0243] If the adhesive sheet of the present invention has the above-mentioned adhesive layer with a tensile residual stress of 300% within a specific range, excellent stress relief can be easily obtained, and excellent height difference tracking performance can be easily achieved. For example, even for large height differences (e.g., height differences of about 45 μm, particularly height differences of 20 to 50 μm), it can track well.
[0244] The aforementioned 300% tensile residual stress is defined as follows: At 23°C, the adhesive layer is stretched along its length to 300% elongation (strain). Maintaining this elongation, the tensile load applied to the adhesive layer 300 seconds after the end of the stretching is calculated. This tensile load is then divided by the initial cross-sectional area of the adhesive layer (the cross-sectional area before stretching) to obtain the value (N / cm²). 2 It should be noted that the initial elongation of the adhesive layer is 100%.
[0245] The adhesive layer of the present invention exhibits excellent transparency due to the excellent compatibility between the acrylic polymer (A) and the hydrogenated polyolefin resin (B). Therefore, visual visibility and appearance are excellent when viewed through the adhesive layer. Thus, the adhesive layer of the present invention is suitable for optical applications.
[0246] (Haze)
[0247] The haze of the adhesive layer of the present invention (according to JIS K7136) is not particularly limited, but preferably 1.0% or less, more preferably 0.8% or less. A haze of 1.0% or less provides excellent transparency and a superior appearance, and is therefore preferred. The lower limit of the haze is not particularly limited; theoretically it is 0%, but practically it can exceed 0.01%. It should be noted that, for the above-mentioned haze, for example, an adhesive layer (thickness: 100 μm) can be used, left to stand at normal temperature (23°C, 50% RH) for at least 24 hours, and then bonded to a glass slide (e.g., a glass slide with 92% total transmittance and 0.2% haze). The resulting object is used as a sample, and the haze is measured using a haze meter (manufactured by Murakami Color Technology Research Institute Co., Ltd., trade name "HM-150N") or its equivalent.
[0248] (Total light transmittance)
[0249] The total transmittance (according to JIS K7361-1) of the adhesive layer of the present invention in the visible light wavelength region is not particularly limited, but preferably 90% or more, more preferably 91% or more, and even more preferably 92% or more. A total transmittance of 90% or more provides excellent transparency and a superior appearance, and is therefore preferred. The upper limit of the total transmittance is not particularly limited; theoretically, it is the value obtained by subtracting the light loss (Fresnel loss) caused by reflection at the air interface from 100%, and practically, it can be 95% or less. It should be noted that, for the above total transmittance, for example, an adhesive layer (thickness: 100 μm) is used. After standing at normal temperature (23°C, 50% RH) for at least 24 hours, it is peeled off when there is an isolator and attached to a glass slide (e.g., a glass slide with a total transmittance of 92% and a haze of 0.2%). The resulting object is used as a sample and measured using a haze meter (manufactured by Murakami Color Technology Research Institute Co., Ltd., trade name "HM-150N") or its equivalent.
[0250] (thickness)
[0251] The adhesive layer described above (particularly the adhesive layer formed by the adhesive composition of the present invention) is not particularly limited, but is preferably 12 to 350 μm, more preferably 12 to 300 μm. A thickness of a certain value or higher improves height difference tracking and bonding reliability, which is preferred. Furthermore, a thickness of a certain value or lower results in particularly excellent processability and manufacturability, which is also preferred.
[0252] (Manufacturing method)
[0253] There are no particular limitations on the manufacturing method of the above-mentioned adhesive layer. For example, the above-mentioned adhesive composition can be applied (coated) to a substrate or release liner, and then dried, cured, or dried and cured as needed.
[0254] It should be noted that the coating (coating) of the above-mentioned adhesive composition can be performed using known coating methods. For example, gravure roller coating machines, reverse roller coating machines, kiss roll coating machines, dip roller coating machines, bar coating machines, knife coating machines, spray coating machines, comma coaters, direct coating machines, and other coating machines can be used.
[0255] [2-4. Other layers of the adhesive sheet]
[0256] In addition to the adhesive layer described above, the adhesive sheet of the present invention may also have other layers. Examples of other layers include other adhesive layers (adhesive layers other than the adhesive layer described above (adhesive layers other than the adhesive layer formed by the adhesive composition of the present invention)), intermediate layers, and primer layers. It should be noted that the adhesive sheet of the present invention may have two or more other layers.
[0257] [2-5. Substrate of Adhesive Sheet]
[0258] The substrate used in the case of an adhesive sheet with a substrate according to the present invention is not particularly limited. For example, various optical films such as plastic films, anti-reflective (AR) films, polarizing plates, and retardation plates can be cited. Examples of raw materials such as the aforementioned plastic films include polyester resins such as polyethylene terephthalate (PET), acrylic resins such as polymethyl methacrylate (PMMA), polycarbonate, cellulose triacetate (TAC), polysulfone, polyarylate, polyimide, polyvinyl chloride, polyvinyl acetate, polyethylene, polypropylene, ethylene-propylene copolymer, and cyclic olefin polymers such as "ARTON" (cyclic olefin polymer, manufactured by JSR Corporation) and "ZEONOR" (cyclic olefin polymer, manufactured by Zeon Corporation). It should be noted that these plastic materials can be used alone or in combination of two or more. Furthermore, the term "substrate" refers to the portion of the adhesive sheet that is adhered to the substrate along with the adhesive layer when the adhesive sheet is attached to the substrate. The release liner (release liner) that is peeled off when the adhesive sheet is used (attached) is not included in the "substrate".
[0259] The aforementioned substrate is preferably transparent. The total transmittance of the substrate in the visible light wavelength region (according to JIS K7361-1) is not particularly limited, but is preferably 85% or more, more preferably 88% or more. Furthermore, the haze of the substrate (according to JIS K7136) is not particularly limited, but is preferably 1.0% or less, more preferably 0.8% or less. Examples of such transparent substrates include PET films, and non-oriented films such as those with trade names "ARTON" and "ZEONOR".
[0260] The thickness of the aforementioned substrate is not particularly limited; for example, 12–500 μm is preferred. It should be noted that the aforementioned substrate can have any shape, including single-layer and multi-layer substrates. Furthermore, the surface of the aforementioned substrate can be subjected to commonly known surface treatments, such as physical treatments like corona discharge treatment and plasma treatment, and chemical treatments like primer treatment.
[0261] [2-6. The separator of the adhesive sheet]
[0262] The adhesive sheet of the present invention can have a release liner (peel backing) on the adhesive surface until use. It should be noted that when the adhesive sheet of the present invention is a double-sided adhesive sheet, each adhesive surface can be protected by two separate release liners, or by a single release liner with both sides serving as peel surfaces, wound into a roll. The release liner serves as a protective material for the adhesive layer and is peeled off when attached to the substrate. Furthermore, when the adhesive sheet of the present invention is a substrate-free adhesive sheet, the release liner also functions as a support for the adhesive layer. It should be noted that the release liner may or may not be necessary.
[0263] The aforementioned separator is not particularly limited; examples include separators having a release layer (release treatment layer) on at least one surface of the separator substrate, separators with low adhesion formed from fluoropolymers, and separators with low adhesion formed from nonpolar polymers. The aforementioned fluoropolymers are not particularly limited; examples include polytetrafluoroethylene, polychlorotrifluoroethylene, ethylene fluoride, polyvinylidene fluoride, tetrafluoroethylene-hexafluoropropylene copolymer, and chlorofluoroethylene-vinylidene fluoride copolymer. Furthermore, the aforementioned nonpolar polymers are not particularly limited; examples include olefin resins such as polyethylene (PE) and polypropylene (PP). Preferably, a separator having a release layer on at least one surface of the separator substrate is used.
[0264] There are no particular limitations on the substrate for the aforementioned separator, and plastic films are an example. Examples of such plastic films include polyester resins such as polyethylene terephthalate (PET), polyethylene naphthalate (PEN), and polybutylene terephthalate (PBT); olefin resins with α-olefins as monomers, such as polyethylene (PE), polypropylene (PP), polymethylpentene (PMP), ethylene-propylene copolymer, and ethylene-vinyl acetate copolymer (EVA); polyvinyl chloride (PVC); vinyl acetate resins; polycarbonate (PC); polyphenylene sulfide (PPS); amide resins such as polyamide (nylon) and fully aromatic polyamide (aramid); polyimide resins; and polyetheretherketone (PEEK). From the viewpoints of processability, availability, operability, dust resistance, and cost, plastic films made from polyester resins are preferred, and PET films are even more preferred.
[0265] The release agent constituting the aforementioned release layer is not particularly limited; examples include silicone-based release agents, fluorine-based release agents, long-chain alkyl-based release agents, and molybdenum sulfide release agents. From the viewpoint of release control and stability over time, silicone-based release agents are preferred. It should be noted that two or more release agents can be used alone or in combination.
[0266] In addition, the above-mentioned peeling layer can be a single layer, or a stacked structure consisting of two or more layers without impairing the characteristics of the present invention.
[0267] One preferred embodiment of the aforementioned separator is a structure that uses a PET film as the separator substrate and has a release layer obtained using a silicone-based release agent on at least one surface of the substrate. It should be noted that the surface of the separator that is opposite to the side in contact with the adhesive layer and does not have a release layer is sometimes referred to as the "back side" of the separator.
[0268] From the viewpoint of ensuring die-cutting and processing properties, maintaining flexibility, and increasing thickness, a carrier material can be laminated on the back side of the aforementioned separator. This carrier material is not particularly limited; for example, a configuration in which two PET film substrates are laminated together using an adhesive layer, or a configuration in which a COP film substrate and a PET film substrate are laminated together using an adhesive layer, are also possible. It should be noted that the aforementioned separator may also be without a carrier material.
[0269] Furthermore, from the viewpoint of suppressing the charging generated during the peeling of the separator during transport and reducing the adhesion and contamination of foreign matter, a conductive treatment layer may be provided on the release layer and / or the back side. This conductive treatment layer is not particularly limited; for example, a coating treatment layer with a composite of poly(3,4-ethylenedioxythiophene) (PEDOT) and polystyrene sulfonic acid (PSS) as the main component can be cited. It should be noted that the separator may also not have a conductive treatment layer.
[0270] The aforementioned isolator can be manufactured using known and conventional methods. The aforementioned carrier material and conductive treatment layer can be prepared by laminating them onto the release layer and / or the back side of the isolator using known methods. Furthermore, the aforementioned isolator of the present invention may also have other layers (e.g., intermediate layer, primer layer, etc.) without impairing the effects of the present invention.
[0271] The thickness of the aforementioned separator is not particularly limited. However, from the viewpoints of cost and the processability of the adhesive sheet during bonding, a thickness of 12 to 200 μm is preferred, 25 to 150 μm is more preferred, and 38 to 125 μm is even more preferred.
[0272] Furthermore, when the adhesive sheet of the present invention is a double-sided adhesive sheet of the double-isolator type, an isolator is provided on one adhesive surface and an isolator is also provided on the other adhesive surface. In this case, it is preferable that each of the two isolators has only one surface as a release layer (in particular, an isolator on one surface of the plastic substrate has a release layer formed by an organosilicon-based release agent). In addition, the isolators are provided in such a way that the release layer is in contact with the adhesive surface.
[0273] Furthermore, when the adhesive sheet of the present invention is a double-sided adhesive sheet of the double-isolator type, it is preferable to set a difference in the peel force of the two isolators. For example, when the adhesive sheet of the present invention is a double-sided adhesive sheet of the double-isolator type, it is preferable to use one isolator on the adhesive surface that is used (attached) first (also referred to as the "1-side"), and the other isolator on the adhesive surface that is used (attached) later (also referred to as the "2-side"). Therefore, it is preferable to use one isolator as the "light peel side" isolator that can be peeled with less force (peel force), and the other isolator as the "heavy peel side" isolator that requires more force (peel force) to peel from the adhesive layer. It should be noted that in this specification, the isolator on the light peel side is sometimes referred to as the "light peel isolator", and the isolator on the heavy peel side is sometimes referred to as the "heavy peel isolator".
[0274] It should be noted that when the adhesive sheet of the present invention is a single-isolator type double-sided adhesive sheet, an isolator is provided on one adhesive surface and wound up, thereby protecting the other adhesive surface of the adhesive sheet by the isolator. When the adhesive sheet of the present invention is a single-isolator type, it is preferable that the surfaces of the isolator are all release layers (peeling treatment layers). Furthermore, the release layer on the side of the two release layers of the aforementioned isolator that comes into contact with the adhesive surface through winding is sometimes specifically referred to as the "back release layer". Typically, the back release layer side of the isolator is used on the "one-sided side" of the double-sided adhesive sheet.
[0275] The adhesive sheet of the present invention can impart stress relief without reducing the molecular weight of the acrylic polymer. Therefore, it is preferred in that it can suppress cracking, deformation, and stick-slipping of the adhesive layer during release of the release liner, and can be used stably. It should be noted that stick-slipping is a vibration phenomenon that occurs on the release surface, which can damage the adhered object and cause breakage, or leave adhesive residue locally on the adhered object.
[0276] When the adhesive sheet of the present invention is a double-sided adhesive sheet, from the perspective of being able to suppress cracking, deformation, and slippage of the adhesive surface of the adhesive layer during the peeling of the separator, and being able to use the adhesive sheet stably, the peel force (separator peel force) of the one side (light peel side) of the separator relative to the adhesive layer is 0.01 to 0.5 N / 50 mm, preferably 0.05 to 0.25 N / 50 mm, and the peel force (separator peel force) of the two sides (heavy peel side) of the separator relative to the adhesive layer (for example, the acrylic adhesive layer, the rubber adhesive layer, etc.) is 0.1 to 1.00 N / 50 mm, preferably 0.2 to 0.85 N / 50 mm. Preferably, the separator peel force on the heavy peel side is always greater than the separator peel force on the light peel side, and there is a peel difference of about 1.1 to 10.0 times.
[0277] In particular, when the adhesive sheet of the present invention is a double-sided adhesive sheet, in order to suppress the so-called unintentional separation phenomenon, the cracking, deformation, and slippage of the adhesive surface of the adhesive layer during the peeling of the separator, and to ensure stable use of the adhesive sheet, the difference between the peeling force of the heavily peeled separator relative to the adhesive layer (separator peeling force) and the peeling force of the lightly peeled separator relative to the adhesive layer (separator peeling force) is preferably 0.01 N / 50 mm or more, more preferably 0.02 N / 50 mm or more, further preferably 0.05 N / 50 mm or more, and particularly preferably 0.06 N / 50 mm or more.
[0278] It should be noted that the aforementioned release liner peel force refers to the 180° peel adhesion force of the release liner relative to the adhesive layer, as measured by a 180° peel test. It should also be noted that the tensile speed was 300 mm / min.
[0279] [2-7. Uses of adhesive sheets, etc.]
[0280] The adhesive sheet of the present invention has the adhesive layer of the present invention (an adhesive layer formed by the adhesive composition of the present invention), thus exhibiting excellent adhesion and resistance to foaming and peeling. Furthermore, it has a low dielectric constant and excellent stress relief and height difference tracking. Therefore, optical components having the adhesive sheet of the present invention are less prone to malfunctions caused by high dielectric constants. In addition, it exhibits excellent bonding reliability, particularly at high temperatures.
[0281] Therefore, the adhesive sheet of the present invention can be usefully used for adherends that are prone to foaming at the interface at high temperatures. For example, polymethyl methacrylate (PMMA) resin sometimes contains unreacted monomers and is prone to foaming caused by foreign matter at high temperatures. In addition, polycarbonate (PC) is prone to producing outgassing of water and carbon dioxide at high temperatures. The adhesive sheet of the present invention, due to its excellent resistance to foaming and peeling, can also be usefully used for plastic adherends containing such resins.
[0282] Furthermore, the adhesive sheet of the present invention is useful not only for adherends with a small coefficient of linear expansion but also for adherends with a large coefficient of linear expansion. It should be noted that the adherend with a small coefficient of linear expansion is not particularly limited; for example, a glass plate (coefficient of linear expansion: 0.3 × 10⁻⁶) can be cited. -5 ~0.8×10 -5 / ℃), polyethylene terephthalate substrate (PET film, coefficient of linear expansion: 1.5×10 -5 ~2×10 -5 / ℃), etc. Furthermore, there are no particular limitations on the substrate with a high coefficient of linear expansion mentioned above; for example, resin substrates with a high coefficient of linear expansion can be cited, and more specifically, polycarbonate resin substrates (PC, coefficient of linear expansion: 7×10) can be cited. -5 ~8×10 -5 / ℃), polymethyl methacrylate resin substrate (PMMA, coefficient of linear expansion: 7×10 -5 ~8×10 -5 / ℃), cyclic olefin polymer substrate (COP, coefficient of linear expansion: 6×10⁻⁶℃) -5 ~7×10 -5 (℃), product name "ZEONOR" (manufactured by Zeon Corporation), product name "ARTON" (manufactured by JSR Corporation), etc.
[0283] The adhesive sheet of the present invention can be usefully used for bonding substrates with small coefficients of linear expansion to substrates with large coefficients of linear expansion. Specifically, the adhesive sheet of the present invention is preferably used for bonding glass substrates (e.g., glass plates, chemically strengthened glass, glass lenses, etc.) to the aforementioned resin substrates with large coefficients of linear expansion.
[0284] Thus, the adhesive sheet of the present invention is useful for bonding various raw materials together, and is particularly useful for bonding glass and plastic substrates. It should be noted that the plastic substrate can also be an optical film such as a plastic film having metal mesh wiring, silver nanowires, etc., on its surface.
[0285] Furthermore, the adhesive sheet of the present invention can be used not only for substrates with smooth surfaces, but also for substrates with surface height differences. In particular, the adhesive sheet of the present invention can be used to bond the glass substrate to the resin substrate with a high coefficient of linear expansion even if at least one of the glass substrate and the resin substrate with a high coefficient of linear expansion has a surface height difference.
[0286] The adhesive sheet of the present invention is preferably used in the manufacture of portable electronic devices. Examples of such portable electronic devices include mobile phones, PHS phones, smartphones, tablets (tablet computers), mobile computers (mobile PCs), portable information terminals (PDAs), electronic notebooks, portable televisions, portable radios and other portable broadcast receivers, portable game consoles, portable audio players, portable DVD players, digital cameras and other cameras, and portable camcorders.
[0287] The adhesive sheet of the present invention is preferably used, for example, for attaching components to each other in portable electronic devices, fixing components to housings, etc. More specifically, examples include attaching cover glass, lenses (especially glass lenses) to touch panels, contact sensors, fixing cover glass, lenses (especially glass lenses) to housings, fixing display panels to housings, fixing input devices such as keypads and touch panels to housings, attaching protective panels of information display units to housings, attaching housings to each other, attaching housings to decorative sheets, and fixing and attaching various components to and from portable electronic devices. It should be noted that, in this specification, a display panel refers to a structure consisting of at least a lens (especially a glass lens) and a touch panel. Furthermore, the lens in this specification includes both transparent bodies that refract light and transparent bodies that do not refract light. That is, the lens in this specification also includes simple window panels that do not refract light.
[0288] Furthermore, the adhesive sheet of the present invention is preferably used for optical applications. That is, the adhesive sheet of the present invention is preferably an optical adhesive sheet for optical applications. More specifically, for example, it is preferably used for bonding optical components (for bonding optical components), manufacturing articles using the above-mentioned optical components (optical articles), etc.
[0289] [3. Optical Components]
[0290] The optical component of the present invention is an optical component having at least the aforementioned adhesive sheet and substrate. The substrate only needs to have metal wiring (e.g., metal mesh wiring, silver nanowires, etc.) on at least one side, and the adhesive layer of the present invention (an adhesive layer formed by the adhesive composition of the present invention) is attached to the side of the substrate having the aforementioned metal wiring. There are no other particular limitations. It should be noted that the adhesive sheet of the present invention may have an isolator on the adhesive surface until use, but the adhesive sheet in the optical component of the present invention is an adhesive sheet for use and therefore does not have an isolator.
[0291] From the viewpoint of obtaining better corrosion resistance, the optical component preferably has the adhesive layer on the side of the substrate opposite to the side with the metal wiring, and more preferably has the adhesive layer attached to the side of the substrate opposite to the side with the metal wiring.
[0292] The materials used to construct the aforementioned metal wiring are not particularly limited. Examples include titanium, silicon, niobium, indium, zinc, tin, gold, silver, copper, aluminum, cobalt, chromium, nickel, lead, iron, palladium, platinum, tungsten, zirconium, tantalum, and hafnium. Furthermore, materials containing two or more of these metals, or alloys with these metals as the main components, are also possible. From an electrical conductivity perspective, gold, silver, and copper are preferred; from both conductivity and cost perspectives, silver and copper are more preferred. That is, the aforementioned metal wiring is preferably silver wiring and / or copper wiring, particularly copper mesh wiring, silver mesh wiring, or silver nanowires. Additionally, for enhanced rust prevention, an oxide film or metal coating film can be applied to the metal wiring. It should be noted that the same applies to the materials used for the metal wiring constituting the touch panel described later.
[0293] Optical components refer to components that possess optical properties (e.g., polarization, refraction, scattering, reflection, transmittance, absorption, diffraction, rotation, visual recognition, etc.). There are no particular limitations on the substrates constituting these optical components. Examples include substrates constituting display devices (image display devices), input devices, and other equipment (optical devices), or substrates used in these devices. Examples include polarizing plates, wavelength plates, phase retardation plates, optical compensation films, brightness enhancement films, light guide plates, reflective films, anti-reflective films, hard-coated films (films with at least one side of a plastic film such as PET film subjected to hard coating treatment), transparent conductive films (e.g., plastic films with an ITO layer on the surface (preferably PET-ITO, polycarbonate, cyclic olefin polymers, etc. ITO films)), appearance films, decorative films, surface protection plates, prisms, lenses, color filters, transparent substrates (glass sensors, glass display panels (LCDs, etc.), glass substrates with transparent electrodes, etc.), and substrates on which these are laminated (sometimes collectively referred to as "functional films"). Furthermore, these thin films can have metal nanowire layers, conductive polymer layers, etc. Additionally, fine metal lines can be screen-printed onto these thin films. It should be noted that the terms "plate" and "thin film" mentioned above encompass plate-like, thin film-like, and sheet-like forms, respectively. For example, "polarizing thin film" includes "polarizing plate" and "polarizing film," etc. Furthermore, "thin film" includes thin film sensors, etc.
[0294] In particular, the adhesive sheet of the present invention is suitable for use in transparent conductive films (metal mesh films, silver nanowire films) having metal wiring in the form of metal mesh wiring or silver nanowires, especially optical components with metal mesh films. Silver and copper are metals that are prone to ion migration, especially silver and copper in the form of metal mesh wiring or silver nanowires, which are prone to ion migration and can easily cause malfunctions due to short circuits caused by metal ions penetrating into the adhesive layer. The adhesive sheet of the present invention has a low dielectric constant and excellent stress relief, so it can fill the height difference caused by metal wiring without leaving air bubbles, and silver and copper are less prone to malfunctions caused by ion migration. It should be noted that the same applies to the metal mesh films and silver nanowire films constituting the touch panel described later.
[0295] Examples of display devices include liquid crystal displays, organic EL (electroluminescent) displays, PDP (plasma display panel), and electronic paper. Additionally, examples of input devices include touch panels.
[0296] The substrate constituting the aforementioned optical component is not particularly limited, and examples include substrates formed from glass, acrylic resins, polycarbonate, polyethylene terephthalate, cyclic olefin polymers, metal films, etc. (e.g., sheet-like, film-like, plate-like substrates, etc.). It should be noted that the "optical component" in this invention, as described above, also includes components that maintain the visual recognizability of the display device and input device and serve a decorative or protective function (such as outer films, decorative films, surface protective films, etc.).
[0297] The adhesive sheet of the present invention is an adhesive sheet with a substrate, and when the adhesive sheet constitutes a component with optical properties, the substrate can be regarded in the same way as the substrate, and the adhesive sheet can also be said to be an optical component of the present invention.
[0298] When the adhesive sheet of the present invention is an adhesive sheet with a substrate, and the above-mentioned functional film is used as the substrate, the adhesive sheet of the present invention can also be used as an "adhesive-type functional film" having the above-mentioned adhesive layer on at least one side of the functional film.
[0299] Next, refer to Figure 1 The schematic diagram illustrates a particularly preferred embodiment of the optical component of the present invention.
[0300] Figure 1 The document describes an optical component 1, which is an optical component having at least an adhesive sheet 10 and a substrate as a metal mesh film 11. The metal mesh film 11 has metal mesh wiring 3 on one side, and the adhesive sheet 10 is attached to the side of the metal mesh film 11 having the metal mesh wiring 3.
[0301] [4. Touch Panel]
[0302] The touch panel of the present invention is a touch panel having at least the aforementioned adhesive sheet and substrate. The substrate only needs to have metal wiring (e.g., metal mesh wiring, silver nanowires, etc.) on one side, and the adhesive layer is attached to the side of the substrate having the metal wiring; there are no other particular limitations. It should be noted that the adhesive sheet in the touch panel of the present invention is an adhesive sheet used in actual use, and therefore does not have an insulating layer.
[0303] As described above, the touch panel is preferably constructed by bonding the optical component of the present invention with another optical component (which may or may not have the aforementioned adhesive sheet, but from the viewpoint of obtaining a better corrosion resistance effect, it is preferable to have the aforementioned adhesive sheet). Furthermore, the aforementioned other optical component may be singular or multiple.
[0304] The method of bonding the optical component of the present invention to the other optical component described above is not particularly limited. For example, the following methods can be cited: (1) bonding the optical component of the present invention to the other optical component using the adhesive sheet of the present invention; (2) bonding the adhesive sheet of the present invention, which includes or constitutes the optical component, to the other optical component; (3) bonding the optical component to a component other than the optical component using the adhesive tape of the present invention; and (4) bonding the adhesive tape of the present invention, which includes or constitutes the optical component, to a component other than the optical component. It should be noted that in the above method (2), the adhesive sheet of the present invention is preferably a double-sided adhesive sheet whose substrate is an optical component (e.g., an optical film).
[0305] Next, refer to Figure 2 The schematic diagram illustrates a particularly preferred embodiment of the touch panel of the present invention.
[0306] Figure 2 (A) describes a touch panel 2 having a transparent substrate 12a, an adhesive sheet 10a, a metal mesh film 11, an adhesive sheet 10b, and the transparent substrate 12b in a state of sequential contact with each other. The metal mesh film 11 has metal mesh wiring 3 on the side of the adhesive sheet 10a, and the adhesive sheet 10a is attached to the side of the metal mesh film 11 with the metal mesh wiring 3. The transparent substrate 12a and the transparent substrate 12b are preferably glass, and the substrate of the metal mesh film 11 is preferably PET. The adhesive sheet 10b may or may not be the adhesive sheet of the present invention, but is preferably the adhesive sheet of the present invention.
[0307] Figure 2 (B) describes a touch panel 2 having a transparent substrate 12a, an adhesive sheet 10a, a metal mesh film 13, an adhesive sheet 10b, a polarizing plate 14a, a transparent substrate 12b, and a polarizing plate 14b arranged sequentially and in contact with each other. The metal mesh film 13 has metal mesh wiring 3 on its side facing the adhesive sheet 10a, and the adhesive sheet 10a is attached to the side of the metal mesh film 13 having the metal mesh wiring 3. The transparent substrate 12a is preferably glass, and the transparent substrate 12b is preferably a glass display panel such as an LCD. The adhesive sheet 10b may be composed of the aforementioned adhesive layer (an adhesive layer formed by the adhesive composition of the present invention), or it may not be composed of the aforementioned adhesive layer (an adhesive layer formed by the adhesive composition of the present invention), but it is preferable to be composed of the aforementioned adhesive layer (an adhesive layer formed by the adhesive composition of the present invention).
[0308] Figure 2(C) describes a touch panel 2 having a transparent substrate 12a, an adhesive sheet 10a, a metal mesh film 13, an adhesive sheet 10b, a hard coating film 15, an adhesive sheet 10c, a polarizing plate 14a, a transparent substrate 12b, and a polarizing plate 14b in a state of sequential contact with each other. The metal mesh film 13 has metal mesh wiring 3 on the side of the adhesive sheet 10a, and the adhesive sheet 10a is attached to the side of the metal mesh film 13 with the metal mesh wiring 3. The transparent substrate 12a is preferably glass, the transparent substrate 12b is preferably a glass display panel such as an LCD, and the hard coating film 15 is preferably a hard-coated PET film. The adhesive sheets 10b and 10c may each be composed of the above-mentioned adhesive layer (an adhesive layer formed by the adhesive composition of the present invention), or may not be composed of the above-mentioned adhesive layer (an adhesive layer formed by the adhesive composition of the present invention), but are preferably composed of the above-mentioned adhesive layer (an adhesive layer formed by the adhesive composition of the present invention).
[0309] Figure 2 (D) describes a touch panel 2, comprising: an optical component 4 having a transparent substrate 12a, an adhesive sheet 10a, a metal mesh film 13, an adhesive sheet 10b, and a hard coating film 15 arranged sequentially and in contact with each other; and an optical component 5 having a polarizing plate 14a, a transparent substrate 12b, and a polarizing plate 14b arranged sequentially and in contact with each other. The optical component 4 and optical component 5 are positioned opposite to each other, with the hard coating film 15 and the polarizing plate 14a in a relative position. The hard coating film 15 does not contact the polarizing plate 14a, and an air layer is formed between the hard coating film 15 and the polarizing plate 14a. The metal mesh film 13 has metal mesh wiring 3 on the side facing the adhesive sheet 10a, and the adhesive sheet 10a is attached to the side of the metal mesh film 13 having the metal mesh wiring 3. The transparent substrate 12a is preferably glass, the transparent substrate 12b is preferably a glass display panel such as an LCD, and the hard coating film 15 is preferably a hard-coated PET film. Adhesive sheets 10b and 10c may each be composed of the aforementioned adhesive layer (an adhesive layer formed by the adhesive composition of the present invention), or may not be composed of the aforementioned adhesive layer (an adhesive layer formed by the adhesive composition of the present invention), but are preferably composed of the aforementioned adhesive layer (an adhesive layer formed by the adhesive composition of the present invention).
[0310] There are no particular limitations on the method of forming the metal mesh wiring on the metal mesh film. Examples include methods such as removing a pre-set metal layer by etching or printing.
[0311] Example
[0312] The present invention will now be described in more detail based on embodiments, but the present invention is not limited to these embodiments. It should be noted that the number of blending parts (parts by weight) refers to the number of blending parts of each of the listed components.
[0313] [Manufacturing Example 1: Preparation of Prepolymer Composition A]
[0314] In a monomer mixture consisting of 40 parts by weight of 2-ethylhexyl acrylate (2EHA), 40 parts by weight of isostearate acrylate (ISTA), 19 parts by weight of N-vinyl-2-pyrrolidone (NVP), and 1 part by weight of 4-hydroxybutyl acrylate (4-HBA), 0.05 parts by weight of photopolymerization initiator (trade name "Omnirad 184", manufactured by IGM Resins BV) and 0.05 parts by weight of photopolymerization initiator (trade name "Omnirad 651", manufactured by IGM Resins BV) were added, and the mixture was irradiated with ultraviolet light until the viscosity (BH viscometer No. 5 rotor, 10 rpm, measuring temperature 30°C) became about 20 Pa·s, a prepolymer composition A was obtained by polymerizing a portion of the above monomer components.
[0315] [Manufacturing Example 2: Preparation of Prepolymer Composition B]
[0316] In a monomer mixture consisting of 31 parts by weight of 2-ethylhexyl acrylate (2EHA), 31 parts by weight of isostearyl acrylate (ISTA), 17 parts by weight of isobornyl acrylate (IBXA), 2 parts by weight of N-vinyl-2-pyrrolidone (NVP), and 19 parts by weight of 4-hydroxybutyl acrylate (4-HBA), 0.05 parts by weight of photopolymerization initiator (trade name "Omnirad 184", manufactured by IGM Resins BV) and 0.05 parts by weight of photopolymerization initiator (trade name "Omnirad 651", manufactured by IGM Resins BV) were added, and the mixture was irradiated with ultraviolet light until the viscosity (BH viscometer No. 5 rotor, 10 rpm, measuring temperature 30°C) became about 20 Pa·s, a prepolymer composition B in which a portion of the above monomer components had been polymerized was obtained.
[0317] [Manufacturing Example 3: Preparation of Prepolymer Composition C]
[0318] In a monomer mixture consisting of 29 parts by weight of 2-ethylhexyl acrylate (2EHA), 29 parts by weight of isostearyl acrylate (ISTA), 21 parts by weight of isobornyl acrylate (IBXA), and 21 parts by weight of 4-hydroxybutyl acrylate (4-HBA), 0.05 parts by weight of photopolymerization initiator (trade name "Omnirad 184", manufactured by IGM Resins BV) and 0.05 parts by weight of photopolymerization initiator (trade name "Omnirad 651", manufactured by IGM Resins BV) were added, and the mixture was irradiated with ultraviolet light until the viscosity (BH viscometer No. 5 rotor, 10 rpm, measurement temperature 30°C) became about 20 Pa·s, a prepolymer composition C in which a portion of the above monomer components had been polymerized was obtained.
[0319] [Example 1]
[0320] In manufacturing example 1, 15 parts by weight of hydrogenated 1,2-polybutadiene glycol (trade name "GI-2000", number average molecular weight (Mn): 3110 (measured value), weight average molecular weight (Mw): 5090 (measured value), polydispersity (Mw / Mn): 1.64 (measured value), hydrogenation rate: ≥93% (list value), iodine value: ≤21 (list value), manufactured by Nippon Soda Co., Ltd.), 0.040 parts by weight of trimethylolpropane triacrylate (TMPTA), and 0.3 parts by weight of silane coupling agent (trade name "KBM-403", manufactured by Shin-Etsu Chemical Co., Ltd.) were added to 100 parts by weight of the prepolymer composition A, and mixed to obtain an adhesive composition (pre-curing composition).
[0321] The adhesive composition described above is applied to a polyethylene terephthalate (PET) release liner (heavy-release release liner, trade name "MRF75", manufactured by Mitsubishi Resin Co., Ltd.) with a final thickness (adhesive layer thickness) of 200 μm to form a coating layer (adhesive composition layer). Next, a PET release liner (light-release release liner, trade name "MRE75", manufactured by Mitsubishi Resin Co., Ltd.) is placed on the coating layer to cover it and block oxygen. Then, a laminate of MRF75 / coating layer (adhesive composition layer) / MRE75 is obtained.
[0322] Next, the laminate was irradiated from the top (MRF38 side) with a black light (manufactured by Toshiba Corporation) at an illuminance of 5 mW / cm². 2 The film is exposed to ultraviolet light for 300 seconds. Then, it is dried in a dryer at 90°C for 2 minutes to allow residual monomers to evaporate. This yields a substrate-free double-sided adhesive sheet consisting only of an adhesive layer, with both sides of the adhesive layer protected by an insulator.
[0323] [Examples 2-5, Comparative Examples 1-8]
[0324] Using the adhesive composition and adhesive layer thickness shown in Table 1, and otherwise operating in the same manner as in Example 1, a substrate-free double-sided adhesive sheet was obtained.
[0325] [Table 1]
[0326]
[0327] The details of the components shown in Table 1 are as follows.
[0328] (Prepolymer Composition)
[0329] A: Prepolymer composition A manufactured in Example 1
[0330] B: The prepolymer composition B manufactured in Example 2
[0331] C: Prepolymer composition C manufactured in Example 3
[0332] (Hydrogenated polyolefin)
[0333] GI-1000: Trade name "GI-1000", hydrogenated 1,2-polybutadiene glycol, number-average molecular weight (Mn): 2320 (measured), weight-average molecular weight (Mw): 4040 (measured), polydispersity (Mw / Mn): 1.75 (measured), hydrogenation rate: ≥97% (catalog value), iodine value: ≤21 (catalog value), manufactured by Nippon Soda Co., Ltd.
[0334] GI-2000: Trade name "GI-2000", hydrogenated 1,2-polybutadiene glycol, number-average molecular weight (Mn): 3110 (measured), weight-average molecular weight (Mw): 5090 (measured), polydispersity (Mw / Mn): 1.64 (measured), hydrogenation rate: ≥97% (catalog value), iodine value: ≤21 (catalog value), manufactured by Nippon Soda Co., Ltd.
[0335] GI-3000: Trade name "GI-3000", hydrogenated 1,2-polybutadiene glycol, number-average molecular weight (Mn): 4660 (measured), weight-average molecular weight (Mw): 6130 (measured), polydispersity (Mw / Mn): 1.32 (measured), hydrogenation rate: ≥97% (catalog value), iodine value: ≤21 (catalog value), manufactured by Nippon Soda Co., Ltd.
[0336] BI-2000: Trade name "BI-2000", hydrogenated 1,2-polybutadiene, number-average molecular weight (Mn): 2930 (measured), weight-average molecular weight (Mw): 4050 (measured), polydispersity (Mw / Mn): 1.38 (measured), hydrogenation rate: ≥97% (catalog value), iodine value: ≤21 (catalog value), manufactured by Nippon Soda Co., Ltd.
[0337] BI-3000: Trade name "BI-3000", hydrogenated 1,2-polybutadiene, number-average molecular weight (Mn): 4750 (measured), weight-average molecular weight (Mw): 6150 (measured), polydispersity (Mw / Mn): 1.30 (measured), hydrogenation rate: ≥97% (catalog value), iodine value: ≤21 (catalog value), manufactured by Nippon Soda Co., Ltd.
[0338] (Non-hydrogenated polyolefin)
[0339] HV-15: Trade name "HV-15", polybutene, number-average molecular weight (Mn): 680 (measured), weight-average molecular weight (Mw): 1000 (measured), polydispersity (Mw / Mn): 1.50 (measured), manufactured by JXTG Energy Co., Ltd.
[0340] G-1000: Trade name "G-1000", 1,2-polybutadiene glycol, number average molecular weight (Mn): 2200 (measured value), weight average molecular weight (Mw): 3800 (measured value), polydispersity (Mw / Mn): 1.7 (measured value), vinyl content: 85% or more (catalog value), manufactured by Nippon Soda Co., Ltd.
[0341] B-1000: Trade name "B-1000", 1,2-polybutadiene, number-average molecular weight (Mn): 2000 (measured value), weight-average molecular weight (Mw): 3100 (measured value), polydispersity (Mw / Mn): 1.5 (measured value), vinyl content: 85% or more (catalog value), manufactured by Nippon Soda Co., Ltd.
[0342] (Multifunctional acrylates)
[0343] TMPTA: Trimethylolpropane triacrylate
[0344] HDDA: Hexanediol diacrylate
[0345] (Photopolymerization initiator)
[0346] Omnirad651: Trade name "Omnirad651", 2,2-dimethoxy-2-phenylacetophenone, manufactured by IGM Resins B.V.
[0347] (Chain transfer agent)
[0348] α-Thioglycerol
[0349] (Stabilizer)
[0350] Triphenyl phosphite
[0351] (Rust inhibitor)
[0352] BT-120: Trade name "BT-120", 1,2,3-benzotriazole, manufactured by Johoku Chemical Industry Co., Ltd.
[0353] (Antioxidants)
[0354] Irganox1010: Trade name "Irganox1010", pentaerythritol tetrakis[3-(3,5-di-tert-butyl-4-hydroxyphenyl)propionate], manufactured by BASF.
[0355] (Silane coupling agent)
[0356] KBM-403: Trade name "KBM-403", 3-epoxypropoxypropyltrimethoxysilane, manufactured by Shin-Etsu Chemical Industry Co., Ltd.
[0357] The number-average molecular weight (Mn), weight-average molecular weight (Mw), and polydispersity (Mw / Mn) values of the above-mentioned hydrogenated and non-hydrogenated polyolefins were determined by GPC (gel permeation chromatography) under the following conditions and calculated using polystyrene conversion.
[0358] Analytical device: GPC: HLC-8320GPC (Tosoh Corporation)
[0359] Measurement conditions:
[0360] Column: TSKgel SuperHZM-H / HZ4000 / HZ3000 / HZ2000
[0361] Column dimensions: 6.0mm I.D. × 150mm
[0362] Eluent: THF (Tetrahydrofuran)
[0363] Flow rate: 0.6 mL / min
[0364] Detector: Differential refractometer (RI)
[0365] Column temperature: 40℃
[0366] Injection volume: 20μL
[0367] The molecular weight is calculated using polystyrene conversion.
[0368] [Feature Evaluation]
[0369] The substrate-free double-sided adhesive sheets of the examples and comparative examples were subjected to the following measurements or evaluations. The evaluation results are shown in Table 2.
[0370] (1) Non-volatile components
[0371] To determine the non-volatile component content of the adhesive composition, place the sample in an aluminum pan with a known weight (W1) and measure its weight (W2). Measure the weight of the sample after heating it at 130°C for 2 hours (W3). Substitute these measurements into the following formula to calculate the content.
[0372] Non-volatile component content (%) = (W3-W1) / (W2-W1)×100
[0373] (2) Gel ratio
[0374] Take approximately 0.1g of the adhesive layer from the double-sided adhesive sheet, wrap it with a porous tetrafluoroethylene sheet (trade name "NTF1122", manufactured by Nitto Denko Corporation) with an average pore size of 0.2μm, and then tie it with kite string. Measure the weight at this point, and use this weight as the weight before impregnation. It should be noted that this weight before impregnation is the total weight of the adhesive layer (the adhesive layer taken above), the tetrafluoroethylene sheet, and the kite string. In addition, the combined weight of the tetrafluoroethylene sheet and the kite string is also measured beforehand, and this weight is used as the bag weight.
[0375] Next, the object (referred to as the "sample"), which was made by wrapping the adhesive layer with a tetrafluoroethylene sheet and binding it with kite string, was placed in a 50 ml container filled with ethyl acetate and left to stand at 23°C for 7 days. Then, the sample (after ethyl acetate treatment) was removed from the container, transferred to an aluminum cup, and dried at 130°C in a desiccator for 2 hours to remove the ethyl acetate. The weight was then measured and taken as the weight after impregnation.
[0376] Then, the gel ratio is calculated according to the following formula.
[0377] Gel yield [% (weight %)] = (XY) / (ZY) × 100
[0378] (4) Total transmittance and haze
[0379] One isolator is peeled off from the double-sided adhesive sheet, and the double-sided adhesive sheet is attached to a glass slide (Made by Matsunami Glass Industry Co., Ltd., "White Grinding No.1", thickness 0.8-1.0 mm, total light transmittance 92%, haze 0.2%). Then the other isolator is peeled off to create a test slide with a layer structure of double-sided adhesive sheet (adhesive layer) / glass slide.
[0380] The total transmittance and haze of the visible light region of the above test films were measured using a haze meter (device name "HM-150", manufactured by Murakami Color Research Institute Co., Ltd.).
[0381] (5) Dielectric constant
[0382] The adhesive layer (obtained by peeling a silicone-treated PET separator from a double-sided adhesive sheet) obtained in the examples or comparative examples was sandwiched between a copper foil and an electrode. The relative permittivity was measured at frequencies of 100 kHz and 1 MHz using the following apparatus. For the measurement, three samples were prepared, and the average of the measured values of the three samples was taken as the relative permittivity.
[0383] It should be noted that the relative permittivity of the adhesive layer at a frequency of 100kHz was measured according to JIS K6911 under the following conditions.
[0384] Measurement method: Volumetric method (Apparatus: Agilent Technologies 4294A)
[0385] Precision Impedance Analyzer
[0386] Electrode construction: 12.1mm Φ, 0.5mm thick aluminum plate
[0387] Counter electrode: 3oz copper plate
[0388] Measurement environment: 23±1℃, 52±1%RH
[0389] (6) Energy storage modulus
[0390] The storage modulus of the adhesive layer (obtained by peeling a silicone-treated PET separator from a double-sided adhesive sheet) obtained in the examples or comparative examples at 25°C was determined by dynamic viscoelasticity measurement. For the test samples of the above adhesive layer, a dynamic viscoelasticity measuring device (ARES, manufactured by TA Instruments Inc.) was used at a frequency of 1 Hz, a temperature range of -20 to 100°C, and a heating rate of 5°C / min to calculate the shear storage modulus at 25°C.
[0391] (7) 180° peel bond strength (180° peel bond strength on glass plate)
[0392] Cut a 100mm long and 20mm wide sheet from the double-sided adhesive sheet. Next, peel one separator from the sheet and attach a PET film (trade name "Lumirror S-10", 25μm thick, manufactured by Toray Industries, Inc.). Then, peel off the other separator and press it onto a test plate using a 2kg roller with one round trip. Then, cure for 30 minutes at 23°C and 50% RH. After curing, use a tensile testing machine (device name "Autograph AG-IS", manufactured by Shimadzu Corporation) according to JIS Z 0237, at 25°C or 65°C and 50% RH, at a tensile speed of 300mm / min and a peel angle of 180°, to measure the 180° peel bond strength (N / 20mm).
[0393] As a test plate, a glass plate (trade name "Sodium-calcium glass #0050", manufactured by Matsunami Glass Industry Co., Ltd.) was used.
[0394] (8) Separator peel force
[0395] The double-sided adhesive sheet samples obtained from the examples and comparative examples were cut into pieces 50 mm wide and 100 mm long. The peel force (N / 50 mm) of the release liner (light peel release liner) was measured using a tensile testing machine (equipment name "Autograph AG-IS", manufactured by Shimadzu Corporation) at a peel angle of 180° and a peel speed of 300 mm / min. On the adhesive surface of the sample after the light peel release liner was removed, a PET film (trade name "Lumirror S-10", thickness 25 μm, manufactured by Toray Industries, Inc.) was applied (backed) with a hand roller in a manner that did not generate bubbles or strain. The peel force of the obtained sample against another release liner (heavy peel release liner) was measured under the same conditions as described above.
[0396] (9) Resistance to foaming and peeling
[0397] One separator of the double-sided adhesive sheet is peeled off, and the double-sided adhesive sheet is pressed and bonded to the ITO layer side of a thin film (hereinafter sometimes referred to as "COP-ITO film") with an ITO (indium and tin oxide) layer on one side of a cycloolefin (COP) substrate (trade name "ZEONOR", manufactured by Zeon Corporation, thickness 100 μm) with a sheet resistivity of 70 Ω / □. Then, a structure A' with a laminated structure of COP-ITO film and double-sided adhesive sheet is obtained.
[0398] Next, the release liner on the peel-off side of the double-sided adhesive sheet of structure A' is peeled off, and structure A' is then pressed and bonded to the glass with a height difference under the following pressing conditions (refer to...). Figures 3-5 The side of the face with the height difference.
[0399] (Fitness conditions)
[0400] Surface pressure: 0.3MPa
[0401] Application speed: 25mm / s
[0402] Roller rubber hardness: 70°
[0403] Then, it was placed in an autoclave and subjected to autoclaving at 50°C and 0.5 MPa for 15 minutes. This yielded a structure B' with a laminated structure consisting of a COP-ITO film, a double-sided adhesive sheet, and glass with a height difference.
[0404] After placing structure B' in an atmosphere of 23°C and 50% RH for 24 hours, structure B' was placed in a dryer set at 85°C for 240 hours.
[0405] Then, structure B' was removed from the dryer and placed in an atmosphere of 23°C and 50% RH for 30 minutes. The presence or absence of foaming (including foaming caused by foreign matter) and delamination of structure B' was then confirmed using a microscope.
[0406] Then, evaluate according to the following evaluation criteria.
[0407] Evaluation Criteria
[0408] E: I didn't see any foaming or peeling at all.
[0409] A: Foaming can be seen solely due to foreign objects larger than 100μm in size.
[0410] X: Foaming, end peeling, and film displacement caused by foreign matter smaller than 100μm can be observed.
[0411] (10) ITO corrosivity [rate of change in thin film resistivity]
[0412] One of the separators of the double-sided adhesive sheet is peeled off, and the double-sided adhesive sheet is pressed and bonded to the other side (opposite side of the ITO layer) of a film (hereinafter sometimes referred to as "COP-ITO film") with an ITO layer formed on one side of a cyclic olefin (COP) substrate (trade name "ZEONOR", manufactured by Zeon Corporation, thickness 100μm) with a sheet resistance of 70Ω / □, to obtain structure A with a laminated structure of ITO film and double-sided adhesive sheet.
[0413] Next, after cutting structure A into 15mm×15mm dimensions, the separator of the double-sided adhesive sheet was peeled off and pressed and bonded to a soda-lime glass plate (25mm×25mm, 0.7mm thickness) using a 2kg roller with one round trip pressing condition. Then, structure B with a laminated structure of ITO film, double-sided adhesive sheet and glass was obtained.
[0414] Additionally, one separator of the same double-sided adhesive sheet as described above is peeled off. The double-sided adhesive sheet is then pressed and bonded to the substrate side of a film (trade name "DSC-03", manufactured by Dai Nippon Printing Co., Ltd., 90μm thick, hereinafter sometimes referred to as "AR film") on one side of a cellulose triacetate (TAC) substrate, where an anti-reflective treatment layer is provided. This yields structure C, which has a laminated structure of AR film and double-sided adhesive sheet. Next, structure C is cut into 10mm × 10mm pieces. The separator of the double-sided adhesive sheet is then peeled off and pressed and bonded to the central portion of the copper side of structure B using a 2kg roller with one back-and-forth pressing condition. This yields structure D, which has a laminated structure formed by five layers: AR film, double-sided adhesive sheet, ITO film, double-sided adhesive sheet, and glass.
[0415] After being placed in an atmosphere of 23°C and 50%RH for 30 minutes, structure D was placed in an autoclave and subjected to autoclave treatment for 15 minutes at a temperature of 50°C and a pressure of 0.5MPa.
[0416] After autoclaving, structure D is removed from the autoclave and placed in an atmosphere of 23°C and 50% RH (RH: relative humidity) for 24 hours.
[0417] As the apparatus for measuring the thin-film resistance of the ITO layer of the above-mentioned structure D, a Hall effect measuring device (trade name "HL5500PC", manufactured by Toho Technology Corporation) was used.
[0418] The sheet resistance of the above structure D was measured at 23°C and 50% RH (initial sheet resistance: R0).
[0419] After the measurement, the samples were placed in environments of 85℃ and 85%RH for 500 hours respectively.
[0420] After removal, the film was subjected to temperature and humidity conditioning for 24 hours at 23℃ and 50%RH. Then, the film resistance was measured at 23℃ and 50%RH (film resistance after test: R1).
[0421] Based on the initial sheet resistance value (R0) and the sheet resistance value (R1) after 500 hours of exposure to an environment of 85°C and 85%RH, the rate of change T of the sheet resistance value is calculated using the following formula.
[0422] Rate of change T (%) = (R1 - R0) / R0 × 100
[0423] When the rate of change of the thin film resistance T is less than 130%, it is judged to be qualified ("○") and has good anti-corrosion performance.
[0424] On the other hand, if the rate of change of resistance relative to the initial value is 130% or more, it is judged as unqualified ("×") and does not have good corrosion resistance.
[0425] [Table 2]
[0426]
[0427] The following are variations of the present invention.
[0428] [Note 1] An adhesive sheet having an adhesive layer,
[0429] The aforementioned adhesive layer contains an acrylic polymer (A) and a hydrogenated polyolefin resin (B) that exhibits liquid flowability at 25°C.
[0430] The dielectric constant of the aforementioned adhesive layer at a frequency of 1 MHz is 2.3–3.5.
[0431] The adhesive sheet has a peel bond strength of at least 6 N / 20 mm to the glass plate at 65°C and a tensile speed of 300 mm / min, with a 180° peel angle.
[0432] The ratio of the 180° peel bond strength of the adhesive sheet to the glass plate at 65°C and a tensile speed of 300 mm / min to the 180° peel bond strength to the glass plate at 25°C and a tensile speed of 300 mm / min (180° peel bond strength to the glass plate at 65°C and a tensile speed of 300 mm / min / 180° peel bond strength to the glass plate at 25°C and a tensile speed of 300 mm / min × 100) is 30 or more.
[0433] [Note 2] According to the adhesive sheet described in Note 1, its 180° peel bond strength to the glass plate at 25°C and a tensile speed of 300 mm / min is 10 N / 20 mm or more.
[0434] [Note 3] The adhesive sheet according to Note 1 or 2, wherein the gelation rate of the aforementioned adhesive layer is 40-85%.
[0435] [Note 4] The adhesive sheet according to any one of Notes 1 to 3 has a haze (according to JIS K7136) of 1.0% or less.
[0436] [Note 5] The adhesive sheet according to any one of Notes 1 to 4 has a total light transmittance (according to JIS K7361-1) of 90% or more.
[0437] [Note 6] The adhesive sheet according to any one of Notes 1 to 5 has a thickness of 12 to 350 μm.
[0438] [Note 7] The adhesive sheet according to any one of Notes 1 to 6, wherein the aforementioned hydrogenated polyolefin resin (B) has a number average molecular weight (Mn) of 1,000 to 5,000 and a polydispersity (Mw / Mn) of 2.0 or less.
[0439] [Appendix 8] The adhesive sheet according to any one of Appendices 1 to 7, wherein the aforementioned hydrogenated polyolefin resin (B) contains at least one selected from the group consisting of hydrogenated polyolefins and hydrogenated polyolefin polyols.
[0440] [Appendix 9] The adhesive sheet according to any one of Appendices 1 to 8, wherein the aforementioned hydrogenated polyolefin resin (B) comprises at least one selected from the group consisting of hydrogenated polybutadiene and hydrogenated polybutadiene polyol.
[0441] [Note 10] The adhesive sheet according to any one of Notes 1 to 9, wherein the aforementioned adhesive layer comprises 3 to 35 parts by weight of the aforementioned hydrogenated polyolefin resin (B) relative to 100 parts by weight of the aforementioned acrylic polymer (A).
[0442] [Note 11] The adhesive sheet according to any one of Notes 1 to 10, wherein, as a monomer component constituting the aforementioned acrylic polymer (A), comprises an alkyl (meth)acrylate having a branched alkyl group having 10 to 24 carbon atoms.
[0443] [Note 12] According to the adhesive sheet of Note 11, the aforementioned alkyl methacrylate having a branched alkyl group having 10 to 24 carbon atoms comprises isostearate methacrylate.
[0444] [Note 13] The adhesive sheet according to Note 11 or 12 contains, relative to the total amount (100 parts by weight) of the monomer components constituting the acrylic polymer (A), 3 to 50 parts by weight of a (meth)acrylate alkyl ester having a branched alkyl group having 10 to 24 carbon atoms.
[0445] [Appendix 14] The adhesive sheet according to any one of Appendices 1 to 13, wherein, as a monomer component constituting the aforementioned acrylic polymer (A), it further comprises at least one selected from the group consisting of alkyl (meth)acrylates having a straight-chain alkyl group having 1 to 24 carbon atoms and alkyl (meth)acrylates having a branched alkyl group having 3 to 9 carbon atoms.
[0446] [Note 15] The adhesive sheet according to any one of Notes 1 to 14, wherein, relative to the total amount (100 parts by weight) of the monomer components constituting the acrylic polymer (A), contains 0.1 to 25 parts by weight of hydroxyl-containing monomers.
[0447] [Note 16] The adhesive sheet according to any one of Notes 1 to 15, wherein, relative to the total amount (100 parts by weight) of the monomer components constituting the acrylic polymer (A), it contains 3 to 30 parts by weight of at least one type of monomer selected from nitrogen-containing monomers and alicyclic monomers.
[0448] [Note 17] The adhesive sheet according to any one of Notes 1 to 16, wherein the monomer component constituting the acrylic polymer (A) does not contain or substantially does not contain carboxyl-containing monomers.
[0449] [Note 18] The adhesive sheet according to any one of Notes 1 to 17, wherein the aforementioned adhesive layer further contains a polyfunctional (meth)acrylate.
[0450] [Note 19] The adhesive sheet according to any one of Notes 1 to 18, wherein the aforementioned adhesive layer further contains a rust inhibitor.
[0451] [Note 20] The adhesive sheet according to Note 19, wherein the aforementioned rust inhibitor is a benzotriazole compound.
[0452] [Note 21] The adhesive sheet according to any one of Notes 1 to 20, wherein the aforementioned adhesive layer further contains a silane coupling agent.
[0453] [Note 22] The adhesive sheet according to any one of Notes 1 to 21, wherein the aforementioned adhesive layer further contains an antioxidant.
[0454] [Note 23] An optical component having at least one adhesive sheet and a substrate as described in any one of Notes 1 to 22, wherein the substrate has metal wiring on at least one side, and the adhesive sheet is attached to the side of the substrate having the metal wiring.
[0455] [Note 24] According to the optical component described in Note 23, the aforementioned metal wiring is a metal mesh wiring or silver nanowires.
[0456] [Appendix 25] A touch panel having at least one adhesive sheet and a substrate as described in any one of Appendices 1 to 22, wherein the substrate has metal wiring on at least one side, and the adhesive sheet is attached to the side of the substrate having the metal wiring.
[0457] [Note 26] According to the touch panel described in Note 25, the aforementioned metal wiring is metal mesh wiring or silver nanowires.
[0458] Explanation of reference numerals in the attached figures
[0459] Optical components 1, 4, and 5
[0460] 2 Touch panel
[0461] 3. Metal mesh wiring
[0462] 10, 10a, 10b, 10c adhesive sheets
[0463] 11 Metal Mesh Film
[0464] 12a, 12b transparent substrate
[0465] 13 Metal Mesh Film
[0466] 14a, 14b polarizing plate
[0467] 15 Hard Coating Film
[0468] 20 glass panes with height differences (height difference test pieces)
[0469] 21 glass plate
[0470] 22 height difference
Claims
1. An adhesive sheet having an adhesive layer, The adhesive layer contains an acrylic polymer (A), a hydrogenated polyolefin resin (B) that exhibits liquid flow at 25°C, and a polyfunctional (meth)acrylate. The acrylic polymer (A) comprises only the following components as monomeric components: alkyl (meth)acrylates having branched alkyl groups having 10 to 24 carbon atoms, at least one of nitrogen-containing monomers and alicyclic monomers, hydroxyl-containing monomers, and optionally alkyl (meth)acrylates other than alkyl (meth)acrylates having branched alkyl groups having 10 to 24 carbon atoms. The adhesive layer comprises 3 to 35 parts by weight of the hydrogenated polyolefin resin (B) relative to 100 parts by weight of the acrylic polymer (A). The dielectric constant of the adhesive layer at a frequency of 1 MHz is 2.3~3.
5. The energy storage modulus of the adhesive layer at 25°C is above 0.01 MPa. The adhesive sheet has a peel bond strength of at least 6 N / 20 mm to the glass plate at 65°C and a tensile speed of 300 mm / min, with a 180° peel angle. The ratio of the 180° peel bond force of the adhesive sheet to the glass plate at 65°C and a tensile speed of 300 mm / min to the 180° peel bond force to the glass plate at 25°C and a tensile speed of 300 mm / min, i.e., the ratio of the 180° peel bond force to the glass plate at 65°C and a tensile speed of 300 mm / min to the 180° peel bond force to the glass plate at 25°C and a tensile speed of 300 mm / min × 100, is 30 or more.
2. The adhesive sheet according to claim 1, wherein the 180° peel adhesion force to the glass plate at 25°C and a tensile speed of 300 mm / min is 10 N / 20 mm or more.
3. The adhesive sheet according to claim 1 or 2, wherein, The gelation rate of the adhesive layer is 40-85%.
4. The adhesive sheet according to claim 1 or 2, wherein the haze according to JIS K7136 is less than 1.0%.
5. The adhesive sheet according to claim 1 or 2, wherein the total light transmittance according to JIS K7361-1 is 90% or more.
6. The adhesive sheet according to claim 1 or 2, wherein the thickness is 12~350μm.
7. The adhesive sheet according to claim 1 or 2, wherein, The hydrogenated polyolefin resin (B) has a number average molecular weight of 1000-5000 and a polydispersity of less than 2.
0.
8. The adhesive sheet according to claim 1 or 2, wherein, The hydrogenated polyolefin resin (B) contains at least one selected from the group consisting of hydrogenated polyolefins and hydrogenated polyolefin polyols.
9. The adhesive sheet according to claim 1 or 2, wherein, The hydrogenated polyolefin resin (B) comprises at least one selected from the group consisting of hydrogenated polybutadiene and hydrogenated polybutadiene polyols.
10. The adhesive sheet according to claim 1, wherein, The alkyl (meth)acrylates having branched alkyl groups with 10 to 24 carbon atoms include isostearyl (meth)acrylate.
11. The adhesive sheet according to claim 1 or 10, wherein, Relative to 100 parts by weight of the total monomer components constituting the acrylic polymer (A), it contains 3 to 50 parts by weight of a (meth)acrylate alkyl ester having a branched alkyl group having 10 to 24 carbon atoms.
12. The adhesive sheet according to claim 1 or 2, wherein, As a monomer component constituting the acrylic polymer (A), the alkyl methacrylate, other than alkyl methacrylates having branched alkyl groups having 10 to 24 carbon atoms, is at least one selected from the group consisting of alkyl methacrylates having straight alkyl groups having 1 to 24 carbon atoms and alkyl methacrylates having branched alkyl groups having 3 to 9 carbon atoms.
13. The adhesive sheet according to claim 1 or 2, wherein, Relative to 100 parts by weight of the total monomer components constituting the acrylic polymer (A), it contains 0.1 to 25 parts by weight of hydroxyl-containing monomers.
14. The adhesive sheet according to claim 1 or 2, wherein, Relative to 100 parts by weight of the total monomer components constituting the acrylic polymer (A), it contains 3 to 30 parts by weight of at least one of nitrogen-containing monomers and alicyclic monomers.
15. The adhesive sheet according to claim 1 or 2, wherein, The adhesive layer also contains a rust inhibitor.
16. The adhesive sheet according to claim 15, wherein, The rust inhibitor is a benzotriazole compound.
17. The adhesive sheet according to claim 1 or 2, wherein, The adhesive layer also contains a silane coupling agent.
18. The adhesive sheet according to claim 1 or 2, wherein, The adhesive layer also contains antioxidants.
19. An optical component comprising at least an adhesive sheet and a substrate as described in any one of claims 1 to 18, wherein the substrate has metal wiring on at least one side, and the adhesive sheet is attached to the side of the substrate having the metal wiring.
20. The optical component according to claim 19, wherein, The metal wiring is a metal mesh wiring or silver nanowires.
21. A touch panel comprising at least the adhesive sheet and substrate according to any one of claims 1 to 18, wherein, The substrate has metal wiring on at least one side, and the adhesive sheet is attached to the side of the substrate having the metal wiring.
22. The touch panel according to claim 21, wherein, The metal wiring is a metal mesh wiring or silver nanowires.
Citation Information
Patent Citations
Acrylic adhesives and its production method
JP2002069411A
Adhesive double coated sheet and method of affixing touch panel to display device
JP2003238915A
Double-sided adhesive sheet and display device with touch panel
JP2003342542A
Pressure sensitive adhesive double-sided sheet and display device with touch panel
JP2004231723A
Adhesive, adhesive layer, and adhesive sheet
JP2016172865A